The NeuroWES project: lessons learned from comprehensive phenotyping and genetic analysis of neurodevelopmental disorders over a decade - Simona Cardaropoli; Lisa Pavinato; Slavica Trajkova; Diana Carli; Verdiana Pullano; Flavia Palermo; Alessandro Mussa; Elisa Biamino; Vincenzo Antona; Andrea Zonta; Paola Dimartino; Mariia Zadorozhna; et al. (Human Genetics, 2026)
Exome sequencing (ES) has become a primary tool for diagnosing neurodevelopmental disorders (NDDs), yet the interpretation of genetic variants in large, heterogeneous cohorts presents significant challenges that automated pipelines often fail to resolve. This study showcases the complexities and novel findings derived from a decade-long analysis of 419 Italian NDD patient-parent trios. While ES established a molecular diagnosis in 36.5% of cases (53.8% in syndromic presentations), our investigation moves beyond diagnostic yield to highlight the critical value of manual curation integrated with deep phenotyping. We demonstrate how this rigorous approach uncovers complex disease mechanisms, revealing that variants initially misclassified as missense or stop-gain are, in fact, pathogenic splicing defects confirmed by functional analysis. Furthermore, we resolve the paradox of pathogenic truncating PPM1D variants in control databases by demonstrating their somatic mosaic nature, a crucial insight for population data interpretation. Our work also refines gene-disease correlations by challenging the established role of MID2 in NDDs, providing further evidence for DSCAM as a high-confidence risk gene, and expanding the known phenotypic spectrum of disorders, such as a novel GNAI2 -related syndrome lacking expected immune dysfunction. This study underscores that navigating the complexities of large NDD cohorts requires a detailed, expert-driven approach to not only enhance diagnostic yield but also to advance our fundamental understanding of rare disease genetics.

Anti-tumour activity of canine activated T-cells and cytokine-induced killer cells against canine malignant melanoma in vitro - Luiza Cesar Conti; Sonia Capellero; Lisa Piras; Emanuela Morello; Sabina Iurascu; Jessica Erriquez; Laura Marconato; Luca Aresu; Raffaella De Maria (The Veterinary Journal, 2026)

Effects on mouse melanoma and immune cells of P2X7 receptor positive allosterism by clemastine - Maria Luiza Thorstenberg; Simonetta Falzoni; Rocio Edith Garcia-Jacobo; Leticia Scussel Bergamin; Mario Tarantini; Giulia Conversano; Anna Pegoraro; Francesco Di Virgilio; Elena Adinolfi; Anna Lisa Giuliani (Purinergic Signalling, 2026)
Clemastine (CLE), an H1R antagonist widely used for the treatment of allergic rhinitis, has recently been investigated for its positive modulatory effects on P2X7, a receptor for extracellular ATP (eATP) involved in the regulation of inflammation, immune responses, and the composition of the tumor microenvironment (TME). Here, we further examined the effects of CLE on P2X7-mediated responses to clarify the pharmacological significance of P2X7 potentiation. First, in murine and human cells expressing (B16F10 WT and HEK293-hP2X7) or lacking (B16F10 P2X7 −/− and HEK293 WT) the P2X7 receptor, we measured intracellular Ca 2+ influx, ethidium bromide (EB) and daunorubicin (DN) uptake, mitochondrial morphology, and LDH and ATP release following P2X7 agonism or antagonism in the presence of CLE. We found that CLE increased Bz-ATP-induced P2X7-mediated channel opening, pore formation, mitochondrial remodeling, eATP release, and cell death, effects absent in P2X7-null cells and abolished by P2X7 antagonists. As a readout of activation of NLRP3 inflammasome, a known downstream effector of the P2X7 receptor, we also assessed the effect of CLE on IL-1β release from peritoneal macrophages from wild-type (WT) or P2X7 knockout (KO) mice, LPS-primed and treated with ATP and/or CLE. We found that the combined treatment significantly increased IL-1β release from P2X7-WT macrophages compared to the two stimuli administered separately. On the whole, our results demonstrate that CLE can effectively positively modulate P2X7 function, suggesting new opportunities for its therapeutic exploitation.

Impact of advanced mixing techniques and ink composition on gelation and rheology of alginate-pea-protein-inks in 3D printing for cultivated meat - Lisa Woelken; Sabrina Bäther; Klara Dehmlow; José Alberto Rodríguez Agudo; Dongwei Wu; Jens Kurreck; Anja Maria Wagemans; Cornelia Rauh (Food Hydrocolloids, 2026)

Upper respiratory microbiome composition and associations with air pollution and infant respiratory health: a longitudinal study in Guatemala - Rina Das; Andrew Baldi; Sant-Rayn Pasricha; Lisa M. Thompson; Anaité Díaz-Artiga; Laura Maria Grajeda; John P. McCracken; Kelsey Jesser; Lance Waller; Matthew C. Freeman; Thomas Clasen; Sheela S. Sinharoy (International Journal of Hygiene and Environmental Health, 2026)

Multi-media occurrence, bioaccumulation, and exposure assessment of PFAS across a Midwestern U.S. State - Maria S. Sepúlveda; Lisa Brown; Staci L. Capozzi; Samantha C. Cullom; Jeffrey E. Dick; Daniel J. Foti; Ronaldo H. Franjul; Nicole L. Franklin; Jennifer L. Freeman; Carolina Gonzalez-Canas; Wanyue Hui; Yuxin Jiang; et al. (Environmental Research, 2026)

Abundance, Diversity and Metabolomic Profiles of Soil Cyanobacteria‐Dominated Microbial Communities Under Long‐Term Differential Management in an Olive Orchard - Mohammad Yaghoubi Khanghahi; Rosangela Addesso; Luigi Lucini; Leilei Zhang; Francesco Maria Calabrese; Margherita Chiarini; Matteo Bernardi; Lisa Signorile; Alba N. Mininni; Bartolomeo Dichio; Carmine Crecchio; Maria De Angelis; et al. (Environmental Microbiology, 2026)
This study assessed the effects of 22 years of sustainable ( S mng ) versus conventional ( C mng ) management on cyanobacteria‐enriched microbial communities in a Mediterranean olive orchard. Surface soils were selectively cultivated in nitrogen‐free Bristol medium to obtain cultivable cyanobacteria‐dominated, nitrogen‐fixing assemblages for molecular and metabolomic analyses. Cyanobacteria‐enriched assemblages derived from S mng soils showed greater phylogenetic diversity and distinct community clustering under N‐free cultivation conditions. At the cyanobacterial genus level, C mng ‐derived communities were dominated by Leptolyngbya , whereas S mng assemblages shifted towards Nodosilinea , alongside the consistent presence of heterocystous Nostoc. These patterns suggest that reduced disturbance and organic inputs favour the enrichment of stable cultivable nitrogen‐fixing cyanobacteria. Untargeted metabolomics identified 494 features and revealed strong functional divergence. C mng ‐derived assemblages showed enhanced lipid and vitamin biosynthesis, consistent with stress‐related metabolic investment. In contrast, S mng ‐derived assemblages displayed increased amino acid biosynthesis and enhanced activity of signalling‐ and hormone‐related metabolic pathways, including cytokinin biosynthesis and ethylene biosynthesis‐related pathways. These metabolic signatures suggest a shift towards resource allocation supporting microbial interactions, plant signalling and nitrogen transfer within the soil–plant system. Overall, the results indicate that S mng favours cyanobacteria‐dominated communities with metabolic traits linked to ecosystem functioning, underscoring their role in improving soil quality and resilience in semi‐arid agroecosystems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A high-resolution record of early rift development and tectonic, sedimentary and environmental conditions in an active rift basin: IODP MSP drilling in the Corinth Rift, Greece (Expedition 381) - Lisa C. McNeill; Donna J. Shillington; Jeanine Ash; Gareth D.O. Carter; Richard E.Ll. Collier; Aleksandra Cvetkoska; Paula Diz; Mai-Linh Doan; Jeremy D. Everest; Natacha Fabregas; Eugenia Fatourou; Mary Ford; et al. (Marine Geology, 2026)

Discerning pristine and aged true-to-life microplastics through polarization-resolved digital holography and machine learning - Maria Pia Pierro; Marika Valentino; Serena Ducoli; Lisa Miccio; Vittorio Bianco; Stefania Federici; Pietro Ferraro (Journal of Environmental Chemical Engineering, 2026)

Antarctic threats: anthropogenic microfibers and plasticizers in the scallop Adamussium colbecki from the Ross Sea - Emma Ferrari; Maria Vittoria Barbieri; Roberta Russo; Aleix Balasch García; Valentina Ferrari; Silvia Simonetti; Giovanni Birarda; Lisa Vaccari; Elisa Bergami; Ethel Eljarrat; Ilaria Corsi (Environmental Research, 2026)

Modulation of conformational features and oligomerization of MMACHC by cobalamin variants: impact of the R161Q mutation in cblC disease - Lisa Longo; Maria Assunta Costa; Rita Carrotta; Maria Rosalia Mangione; Vincenzo Martorana; Marco Tutone; Maria Grazia Ortore; Paula M. Garcia-Franco; Sonia Vega; Adrian Velazquez-Campoy; Rosa Passantino; Silvia Vilasi (European Biophysics Journal, 2026)
Vitamin B12 (cobalamin, Cbl) is a coordination compound of the cobalt, located at the center of a corrin ring composed of four pyrrolic-like groups. The cobalt ion can be bound to a variety of upper axial ligands, which vary among different cobalamin forms, including hydroxocobalamin (OHCbl), cyanocobalamin (CNCbl), methylcobalamin (MeCbl), and adenosylcobalamin (AdoCbl). MeCbl and AdoCbl are considered the biologically active forms, serving as cofactors in the metabolism of methylmalonic acid (MMA) and homocysteine (HCY). Impaired conversion of these metabolites leads to their pathological accumulation, resulting in severe cellular damage. This is precisely what occurs in cblC deficiency, a rare inborn disorder caused by mutations in the MMACHC protein, which plays a crucial role in binding and processing the various cobalamin forms. Mutations affecting MMACHC function impair its ability to correctly handle cobalamins, leading to the disease. In this study, we evaluated the impact of various cobalamin forms, specifically AdoCbl, MeCbl, and CNCbl, on the stability and oligomeric organization of the wild type MMACHC protein, using circular dichroism spectroscopy, native gel electrophoresis, and small-angle X-ray scattering. Moreover, isothermal titration calorimetry experiments provided insights into the thermodynamic parameters governing MMACHC binding to these cobalamins. In addition, we also assessed how the R161Q mutation in MMACHC alters the affinity of this protein for the different vitamin B12 forms, leading to decreased stability and impaired homodimerization, a process likely relevant to its functional role. Our findings provide molecular insights into cblC pathogenesis and advance our understanding of MMACHC structure–function relationships.

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Long-term agroforestry effects on soil CO2 and NO emissions in the Brazilian semiarid region - Vanessa Maria de Souza Barros; José Augusto Amorim Silva do Sacramento; Naiara Oliveira Figueiredo; Mona Lisa Moura de Oliveira; Francisco Alisson da Silva Xavier; Maria Eugenia Ortiz Escobar; Ana Clara Rodrigues Cavalcante; Júlio César Lima Neves; Teogenes Senna de Oliveira (Journal of Arid Environments, 2026)

Bile Salt Hydrolase Activity in the Food-Derived Strain Levilactobacillus brevis M3R3: Genomic and Functional Characterization - Gianluigi Agolino; Marianna Cristofolini; Maria Anna Ronsivalle; Alice Cattivelli; Davide Tagliazucchi; Cinzia Caggia; Lisa Solieri; Cinzia L. Randazzo (Probiotics and Antimicrobial Proteins, 2026)
In the present study, Levilactobacillus brevis M3R3, isolated from traditional Sicilian sourdough, was evaluated for bile salt hydrolase (BSH) activity through kinetic growth assays and bile salts (BSs) deconjugation analysis by UHPLC/HR-MS. Genome sequencing and in silico analyses were performed to assess its safety and probiotic potential. Results showed that strain M3R3 tolerated different concentrations of individual conjugated BSs, with dose-dependent growth inhibition. Exposure to 1.0% glycocholic and glycodeoxycholic acids reduced M3R3 growth, indicating an adaptive stress response. When exposed to a mixed BS solution mimicking intestinal conditions, the strain maintained growth despite an extended lag phase and a reduced final biomass, likely due to toxic BSs accumulation. UHPLC/HR-MS confirmed complete deconjugation of glyco-conjugated BSs and partial deconjugation of tauro-conjugated BSs. Whole-genome sequencing (2.30 Mbp, 2375 CDSs) revealed absence of antimicrobial resistance or virulence genes and identified two bsh genes ( bsh_2A and bsh_3A ), both expressed under control and BS-exposed conditions. Phylogenetic analysis of L. brevis BSH proteins identified three clusters (I, II, and III), with bsh_2A and bsh_3A from M3R3 grouped in clusters II and III, respectively. Overall, genomic and functional characterizations support that L. brevis M3R3 is a safe, BSH-active strain, with potential applications as a functional ingredient in health promoting formulations.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Corrigendum to “Embedded bioprinting enables precise fabrication of cultured meat with authentic structural properties” [Food Hydrocolloids 171 (2026) 111795] - Dongwei Wu; Shumin Pang; Sabrina Bäther; Lisa Woelken; Mariia Abyzova; Jordi Morales-Dalmau; Astrid Haibel; Yunpeng Jia; Johanna Berg; Benedikt B. Kaufer; Caroline Denesvre; Anja Maria Wagemans; et al. (Food Hydrocolloids, 2026)

Permian mylonites in the footwall of a Miocene Cycladic core complex (Ios, Greece): Insights from (micro)structurally integrated apatite U-Pb petrochronology - Megan Elysia Flansburg; Daniel Fritz Stockli; Eirini Maria Poulaki; Konstantinos Soukis; Lisa Danielle Stockli (Earth and Planetary Science Letters, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Corrigendum to “High mountains, Late Palaeolithic hunting. The case of Hučivá Diera Cave in the Tatra Mts. (West Carpathians)” [Quaternary International 758 (2026) 15 (2026) 110151] - Paweł Valde-Nowak; Maria Hajnalova; Katarzyna Kerneder-Gubała; Julia Kościuk-Załupka; Magda Kowal; Anna Kraszewska; Aldona Kurzawska; Anna Lemanik; Lenka Lisa; Kamil Makuła; Ewelina Miśta-Jakubowska; Adam Nadachowski; et al. (Quaternary International, 2026)

High mountains, late palaeolithic hunting. The case of Hučivá Diera Cave in the Tatra Mts. (West Carpathians) - Paweł Valde-Nowak; Maria Hajnalova; Katarzyna Kerneder-Gubała; Julia Kościuk-Załupka; Magda Kowal; Anna Kraszewska; Aldona Kurzawska; Anna Lemanik; Lenka Lisa; Kamil Makuła; Ewelina Miśta-Jakubowska; Adam Nadachowski; et al. (Quaternary International, 2026)

Embedded bioprinting enables precise fabrication of cultured meat with authentic structural properties - Dongwei Wu; Shumin Pang; Sabrina Bäther; Lisa Woelken; Mariia Abyzova; Jordi Morales-Dalmau; Astrid Haibel; Yunpeng Jia; Johanna Berg; Benedikt B. Kaufer; Caroline Denesvre; Anja Maria Wagemans; et al. (Food Hydrocolloids, 2026)

Bacterial community and chemical contamination in high-latitude lake waters: a comparative study from the Svalbard and Antarctic Peninsula regions - Alessandro Ciro Rappazzo; Angelina Lo Giudice; Carmen Rizzo; Stefania Giannarelli; Lisa Ghezzi; Maurizio Azzaro; Warren Raymond Lee Cairns; Maria Papale (Environmental Research, 2026)

Studies on energy recovery from microalgae and plants wastes - Loredana-Vasilica Postolache; Gabriela Soreanu; Igor Cretescu; Nita Tudorachi; Daniela Rusu; Mirela-Fernanda Zaltariov; Ion Anghel; Dana Maria Preda; Gabriela Lisa (Biomass and Bioenergy, 2026)

Cardiovascular risk factors and vascular neuropathological findings in primary age-related tauopathy versus Alzheimer’s disease - Lisa Y. Xiong; Myuri Ruthirakuhan; Si Won Ryoo; Che-Yuan Wu; Jodi D. Edwards; Jennifer S. Rabin; Maria Carmela Tartaglia; Sandra E. Black; Julia Keith; Walter Swardfager (GeroScience, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Updated Swedish guidelines for the management and treatment of RSV infection - Lars Navér; Emmi Andersson; Frida Blomgren; Henrik Ljungberg; Joachim Luthander; Anna Nordlander; Michal Odermarsky; Andreas Ohlin; Samuel Rhedin; Lina Schollin Ask; Susanne Strömdahl; Lisa Swartling; et al. (Infectious Diseases, 2026)

Development of a new prototypal natural whey starter production system to study biodiversity and technological features fluctuations during back-slopping practice used in Parmigiano Reggiano PDO cheese production: penicillin G as a case study - Marianna Cristofolini; Maria Anna Ronsivalle; Davide Manicardi; Valentina Pizzamiglio; Valeria Musi; Elena Bortolazzo; Lisa Solieri (Food Microbiology, 2026)

Recurring cryptic mass mortalities—Lessons from bioturbating echinoids under combined climatic and anthropogenic stress - Lisa‐Maria Schmidt; Guillermo Anderson; Shahar Malamud; Andreas Kroh; Omri Bronstein (Limnology and Oceanography, 2026)
Marine mass mortality events (MMEs) are a growing source of concern globally. Affecting diverse marine ecosystems, they frequently cause significant ecological disruptions, often leading to large‐scale ecological shifts. However, in contrast to terrestrial MMEs, most marine mortalities likely occur undetected, particularly in cryptic and infaunal taxa. Here, we present the first documented reports of irregular echinoid mass mortalities from the Eastern Mediterranean Sea—a region at the forefront of ocean warming and anthropogenic pressure. Compiling ecological, morphometric, molecular, and remote‐sensed environmental data, we reconstruct a 14‐yr history (2011–2024) of MMEs involving the key infaunal bioturbating echinoids of the genus Echinocardium . We analyzed environmental parameters, namely sea surface temperatures, chlorophyll a concentrations, river discharge, and wave intensity, in the weeks preceding five MMEs and analyzed skeletal remains to explore the potential drivers of mortalities. We show that these events are neither rare nor stochastic but rather recurring and spatially structured—spanning hundreds of meters and positioned at the outlet of major rivers, likely driven by cumulative environmental and human stressors. By revealing patterns in taxa often overlooked in marine monitoring, this work highlights the urgency of assessing ecological stability in sedimentary ecosystems. We highlight the need for implementing long‐term monitoring and improved environmental assessments, at both national and regional scales, to include benthic infaunal communities—particularly in rapidly warming regions like the Eastern Mediterranean.

Midwives ‘views of parents’ questions and expectations on prenatal genetic testing - identifying informational needs in prenatal genetic counselling - Lisa Åkerman; Maria Johansson Soller; Charlotta Ingvoldstad Malmgren (Journal of Community Genetics, 2025)
Autonomy and informed decision making are important aspects for prenatal genetic screening and diagnostics. Midwives’ knowledge and skills are essential to provide adequate information about prenatal testing to expecting parents to enable informed decisions. Information from midwives to parents about prenatal genetic testing has been found to not always be adequate, and parents’ needs not always understood.​ As new methods are introduced, the scope of analysis is widening. In order to achieve informed decision-making, it is important to understand the questions and expectations midwives meet from expecting parents. This study explores the questions and expectations midwives meet from expecting parents regarding prenatal genetic testing, and how uncertainties are perceived and valued. A questionnaire was distributed through a midwife with a national coordinating role, to all midwives in primary maternity care and to the 8 ultrasonography clinics in the Stockholm region, as well as to midwives across Sweden via regional coordination midwives. The responding midwives ( N = 71) represented different health care regions in Sweden, working both in primary maternity healthcare and as ultrasonography specialists. Midwives were found to perceive an increased number of questions about noninvasive prenatal testing (NIPT) but a proportion of midwives are not completely confident to answer these questions. Midwives get questions about trisomy 21, other trisomies and sex chromosome abnormalities, but also neuropsychiatric conditions. Methods for invasive, diagnostic testing do not seem to be discussed when accepting offer of initial screening. ​ Midwives are aware of uncertain and secondary findings, but fewer have discussed this with parents. Continuing education and support for midwives is essential – and should put additional focus on developing understanding around established methods like NIPT, but also on more comprehensive genomic test methods such as microarray and massive parallel sequencing techniques as well as challenges around discussing conditions tested for and test results, including uncertain results and secondary findings, with expecting parents.

Effects of cigarette smoke extract on surfactant production in ATII-like cells, involvement of oxidative stress and autophagy - Maria Lisa Garavaglia; Francesca Bodega; Chiara Sironi; Cristina Porta; Isabella Dalle-Donne (Toxicology, 2025)

No apparent effect of modafinil on long-acting rilpivirine and cabotegravir concentrations: a case report in a person with HIV - Andrea Poloni; Anna Lisa Ridolfo; Antonio D’Avolio; Andrea Giacomelli; Maria Vittoria Cossu; Andrea Gori; Dario Cattaneo; Cristina Gervasoni (European Journal of Clinical Pharmacology, 2025)

Factors associated with avian influenza infections in indoor commercial poultry farm settings: A systematic review - Elvira Meni Maria Gkrinia; Lisa Kohnle; Christina Joanne Atchison; Wendy Kwok (Preventive Veterinary Medicine, 2025)

Development and implementation of a structured, quantitative approach to infection prevention and control within small animal veterinary care across four different European countries - Anna-Maria Andersson; Madelene Holappa; Ditte Ljungquist; Lisa Tolfree; Sarah Proot; Marlene Areskog (Preventive Veterinary Medicine, 2025)

Estimating the long-term health impact and program cost-effectiveness of providing direct screening services to low-income, medically underserved patients through the Colorectal Cancer Control Program (CRCCP) - Meghan C. O’Leary; Priscille R. Koutouan; Maria E. Mayorga; Krishna P. Sharma; Amy DeGroff; Lisa C. Richardson; Kristen Hassmiller Lich (Cancer Causes & Control, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

The effects of umami on salt and bitter taste perception in plant-based protein foods: A systematic review - Yulianna Holowaty; Jessica Adams; Lisa Methven; Keng Ngee Teoh; Ana San Gabriel; Andrea Wakita; Maria Jose Oruna-Concha (Appetite, 2025)

Soil bacteria and symbiotic rhizobia synergistically promote nitrogen fixation and biomass production of alfalfa (Medicago sativa L.) plants even under water shortage conditions without altering the native rhizospheric microbiota - Lisa Cangioli; Camilla Fagorzi; Francesca Vaccaro; Stefano Varriale; Maria Laura Amenta; Alessio Mengoni; Rosolino Ingraffia; Antonella Lo Porto; Gaetano Amato; Dario Giambalvo; Jean Rodrigue Sangaré; Roberto Defez; et al. (Applied Soil Ecology, 2025)

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

Noble gases in CO chondrites: Primordial components, effects of parent body thermal alteration, and cosmic ray exposure ages - Lisa Maria Eckart; Henner Busemann; Daniela Krietsch; Cornelia A.K. Mertens; Colin Maden; Conel M.O’D. Alexander; Kevin Righter (Geochimica et Cosmochimica Acta, 2025)

Disseminated aspergillosis associated with severe non-regenerative anemia in a Lagotto Romagnolo: a case report - Maria Teresa Antognoni; Valentina Cremonini; Francesco Birettoni; Fabrizio Passamonti; Ambra Lisa Misia; Aurora Barbetta; Arianna Miglio (Veterinary Research Communications, 2025)

The aging choroid plexus and its relationship with gut dysbiosis and Klotho decline: possible intervention strategies - Giovanni Lai; Lisa Bevilacqua; Maria Elisa Giuliani; Giorgia Bigossi; Serena Marcozzi; Tiziana Casoli; Pasqua Abbrescia; Antonio Frigeri; Marco Malavolta; Marta Balietti (GeroScience, 2025)
The choroid plexus (ChP) is a complex ventricular structure that forms a semi-permeable barrier between the blood and cerebrospinal fluid (CSF). It is responsible for CSF secretion and clearance, contains macrophages, and is one of the few sites within the central nervous system (CNS) where T cells are present. Additionally, the ChP plays a role in detecting peripheral inflammation, which leads to the modulation of its epithelial cell function. Despite its critical importance in maintaining brain homeostasis, the ChP is often overlooked, particularly concerning the changes it undergoes with aging, such as reduced barrier function, impaired CSF production, and altered immunosurveillance. These age-related alterations may contribute to several harmful effects, including neuroinflammation and oxidative damage, potentially predisposing individuals to neurodegenerative conditions. Although knowledge is still limited, gut dysbiosis and decreased Klotho levels—of which the ChP is one of the main sources—appear to be significant contributors to ChP impairments. This narrative review will examine the impact of age-related gut dysbiosis on the CNS, focusing on the ChP, and explore the effects of reduced Klotho levels in this brain structure. We will also propose the hypothesis that combining the administration of probiotics capable of restoring gut microbiota eubiosis with gene therapy to upregulate Klotho in the ChP could help preserve the structural and functional integrity of the aging brain. Finally, we will provide a technical overview to ensure that vectors encoding Klotho cDNA achieve maximum specificity for the ChP, thereby avoiding off-target effects. Graphical abstract

Assessing safety and sustainability performance of advanced nanomaterials: A tiered approach along the innovation process - Arianna Livieri; Sarah Devecchi; Lisa Pizzol; Alex Zabeo; Stella Stoycheva; Maria José López-Tendero; Andrea Brunelli; Elena Badetti; Elena Semenzin; Danail Hristozov (NanoImpact, 2025)

Effects of low levels of mango peels (Mangifera indica L.) and apple pectin on in vitro-fermentability, digestive-physiological, and microbiological parameters in piglet nutrition - Jürgen Zentek; Lisa Brucker; Reinhold Carle; Philip Krüsselmann; Beatriz Martínez-Vallespín; Łukasz Grześkowiak; Johannes Schulze Holthausen; Eva-Maria Saliu; Wilfried Vahjen (Livestock Science, 2025)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Cistus incanus : a natural source of antimicrobial metabolites - Anna De Filippis; Vincenzo D’Amelia; Veronica Folliero; Carla Zannella; Gianluigi Franci; Massimiliano Galdiero; Antonio Di Loria; Carmen Laezza; Simona Maria Monti; Anna Lisa Piccinelli; Rita Celano; Maria Manuela Rigano (Natural Product Research, 2025)

Interdisciplinary investigations of a pristine alpine lake in Austria: The Lake Altaussee Monitoring Program (LAMP) - Dimitri D. Deheyn; Philipp Haeuselmann; Thomas Burschil; Stefano Fabbri; Markus Fiebig; Wolfgang Gasperl; Michael Grabner; Jean Nicolas Haas; Andreas Holzinger; Helmut Kalss; Werner Kofler; Cassandra C. Kremer; et al. (Total Environment Advances, 2025)

Lacustrine sedimentary evidence of cascading mountain hazards at the inner-Alpine Lake Altaussee (Eastern Alps, Austria) during the Late Holocene - Marcel Ortler; Jasper Moernaut; Markus Fiebig; Andrea Franco; Jean Nicolas Haas; Irka Hajdas; Philipp Haeuselmann; Julia Rechenmacher; Lisa-Maria Weber; Erwin Heine (Sedimentary Geology, 2025)

The invasion history of Ambrosia psilostachya (Asteraceae) in Italy: first record and distribution over more than one century - Chiara Montagnani; Rodolfo Gentili; Gerhard Karrer; Sarah Caronni; Alicia Teresa Rosario Acosta; Michele Adorni; Alessandro Alessandrini; Nicola Maria Giuseppe Ardenghi; Gabriella Buffa; Fabrizio Bartolucci; Alessandra Belisario; Fabrizio Bonali; et al. (Plant Biosystems, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Increase of tropical seabirds (Sula) in the California Current Ecosystem with warmer ocean conditions - Tamara M. Russell; David M. Pereksta; James R. Tietz; Maria Vernet; Jaime Jahncke; Lisa T. Ballance (Frontiers in Marine Science, 2025)
Climate change is impacting marine ecosystems through physical changes (e.g., increased marine heatwaves, long-term warming) that can manifest biologically at all trophic levels. In the California Current Ecosystem (CCE), a productive and economically important eastern boundary upwelling system, the effects of these physical changes are observed throughout the region from Mexico to Canada. We investigated range expansions into the CCE and correlations with the environment for a group of tropical/sub-tropical seabirds, widely recognized as ecosystem indicators. We assessed changes in the abundance (2002-2022) of five species from the genus Sula (Cocos, Blue-footed, Red-footed, Masked, and Nazca Boobies), using a novel compilation of four data sources and investigated potential relationships with the environment. All five species increased in abundance within the CCE by 692-3015% after the extreme marine heatwaves that began in late 2013, and all species, with the exception of Blue-footed, exhibited a northward range expansion by as much as 6.8 degrees latitude and increased range area of 235-1013%. Furthermore, the increased presence of all species except Masked and Nazca Boobies correlated with warmer conditions around Baja California, Mexico, one month prior to their occurrence northward. Our results document the increase of these large bodied, tropical species and a tropical shift in the predator community of the CCE, which mirrors changes that occurred there during the last extreme global warming period on Earth, the Miocene. As marine heatwaves are projected to increase in frequency and intensity, in addition to long-term warming, we hypothesize that these species will continue to expand their range northward and increase in abundance in this upwelling ecosystem.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Alarm cue properties and euthanasia impact on tadpole antipredator behaviour in Rana temporaria and Bufo bufo - Konrad Lipkowski; Diana Abondano Almeida; David Wenzel; Lisa Maria Schulte (Animal Behaviour, 2025)

Large heterogeneity in biosecurity legislation in the intensive pig production across Europe - Evelien Biebaut; Marina Štukelj; Ilias Chantziaras; Telmo Pina Nunes; Vitalii Nedosekov; Carla Correia Gomes; Blerta Mehmedi; Isabelle Corrégé; László Ózsvári; Line Svennesen; Elise Bernaerdt; Ina Toppari; et al. (Preventive Veterinary Medicine, 2025)

The effect of cation ordering in omphacite on the phonon compressibility: A step towards Raman elastic geothermobarometry - Lisa Baratelli; Mara Murri; Matteo Alvaro; Boriana Mihailova; Tiziana Boffa Ballaran; Maria Chiara Domeneghetti; Fernando Cámara (Chemical Geology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Carob (Ceratonia siliqua) leaves: A comprehensive analysis of bioactive profile and health-promoting potential of an untapped resource - Simona Serio; Valentina Santoro; Rita Celano; Donatella Fiore; Maria Chiara Proto; Filomena Corbo; Maria Lisa Clodoveo; Roberta Tardugno; Anna Lisa Piccinelli; Luca Rastrelli (Food Chemistry, 2025)

Review of organic gaseous pollutant concentrations in indoor conservation spaces - Lisa Vergelli; Francesca Frasca; Chiara Bertolin; Gabriele Favero; Anna Maria Siani (Environmental Pollution, 2025)

Assessing predictions on fitness effects of missense variants in HMBS in CAGI6 - Jing Zhang; Lisa Kinch; Panagiotis Katsonis; Olivier Lichtarge; Milind Jagota; Yun S. Song; Yuanfei Sun; Yang Shen; Nurdan Kuru; Onur Dereli; Ogun Adebali; Muttaqi Ahmad Alladin; et al. (Human Genetics, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Spatial and habitat determinants of small-mammal biodiversity in urban green areas: Lessons for nature-based solutions - Olivia Dondina; Pietro Tirozzi; Andrea Viviano; Emiliano Mori; Valerio Orioli; Nicola Tommasi; Alessandro Tanzi; Lisa Bazzoli; Enrico Caprio; Corinna Patetta; Maria Chiara Pastore; Luciano Bani; et al. (Urban Forestry & Urban Greening, 2025)

Genomic diversity in time and space in the toxic diatom Pseudo-nitzschia multistriata - Svenja Mager; Francesco Manfellotto; Antonella Ruggiero; Viviana Di Tuccio; Federica Cerino; Stefano Accoroni; Tomohiro Nishimura; Marta Mikhno; Neri Fattorini; Timotej Turk Dermastia; Jasna Arapov; Sanda Skejic; et al. (Harmful Algae, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Wastewater based measures of COVID-19 and associations with children's absenteeism at grade schools - Helena M. Solo-Gabriele; Gabriela Guevara; Naresh Kumar; Ayaaz Amirali; Kristina M. Babler; Cynthia C. Beaver; Samuel Comerford; Maria Ferraris; Natasha Schaefer Solle; Mark E. Sharkey; Lisa Gwynn (Science of The Total Environment, 2025)

Origin and intra-annual variability of vertical microplastic fluxes in Fram Strait, Arctic Ocean - Lisa Roscher; Eva-Maria Nöthig; Kirsten Fahl; Claudia Wekerle; Thomas Krumpen; Mario Hoppmann; Nadine Knüppel; Sebastian Primpke; Gunnar Gerdts; Melanie Bergmann (Science of The Total Environment, 2025)

Ethical assessment of genome resource banking (GRB) in wildlife conservation - Pierfrancesco Biasetti; Elena Mercugliano; Lisa Schrade; Maria Michela Spiriti; Frank Göritz; Susanne Holtze; Steven Seet; Cesare Galli; Jan Stejskal; Silvia Colleoni; Daniel Čižmár; Raffaella Simone; et al. (Cryobiology, 2024)

Association between long-term exposure to air pollution and cause-specific mortality within five Italian longitudinal metropolitan studies - Federica Nobile; Nicola Caranci; Elena Strippoli; Valentina Adorno; Alessandra Allotta; Lucia Bisceglia; Ida Galise; Claudio Gariazzo; Sara Maio; Paola Michelozzi; Walter Pollina Addario; Andrea Ranzi; et al. (Atmospheric Environment, 2024)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

Stiffness evaluation of coarse unbound granular materials using large-scale repeated load triaxial test - Lisa Tronhuus Hannasvik; Inge Hoff; Diego Maria Barbieri (Transportation Geotechnics, 2024)

Comparison of european surveillance and control programs for Salmonella in broiler and Turkey chains - João B. Cota; Nina Langkabel; Lisa Barco; Abbey Olsen; Silvia Bonardi; Madalena Vieira-Pinto; Mati Roasto; Adeline Huneau-Salaün; Marianne Sandberg; Ole Alvseike; Arja H. Kautto; Bojan Blagojevic; et al. (Food Control, 2024)

Dissecting the dynamics of SARS-CoV-2 reinfections in blood donors with pauci- or asymptomatic COVID-19 disease course at initial infection - Alexandra Domnica Hoeggerl; Verena Nunhofer; Lisa Weidner; Wanda Lauth; Georg Zimmermann; Natalie Badstuber; Christoph Grabmer; Orkan Kartal; Christof Jungbauer; Heidrun Neureiter; Nina Held; Tuulia Ortner; et al. (Infectious Diseases, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The integration of omics and cultivation-dependent methods could effectively determine the biological risks associated with the utilization of soil conditioners in agriculture - Arianna Peruzzo; Sara Petrin; Aurora Boscolo Anzoletti; Marzia Mancin; Andrea Di Cesare; Raffaella Sabatino; Maria Cristina Lavagnolo; Giovanni Beggio; Giulia Baggio; Patrizia Danesi; Lisa Barco; Carmen Losasso (Journal of Hazardous Materials, 2024)

Assessment of fetal development during mid and late term pregnancies by standard B-Mode ultrasonography in Shetland ponies - Lisa-Hélène Wagner; Jörg Aurich; Svenja Claaßen; Maria Melchert; Martim Kaps; Christine Aurich (Journal of Equine Veterinary Science, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Study of the effects of pasteurization and selected microbial starters on functional traits of fermented table olives - Annamaria Tarantini; Pasquale Crupi; Francesca Anna Ramires; Leone D'Amico; Giuseppe Romano; Federica Blando; Pierpaolo Branco; Maria Lisa Clodoveo; Filomena Corbo; Angela Cardinali; Gianluca Bleve (Food Microbiology, 2024)

The thrombin receptor PAR4 supports visceral adipose tissue inflammation - Sonja Kleeschulte; Vivien Fischinger; Lisa Öhlke; Johannes Bode; Markus Kamler; Dobromir Dobrev; Maria Grandoch; Anke C. Fender (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Thrombin inhibition suppresses adiposity, WAT inflammation and metabolic dysfunction in mice. Protease-activated receptor (PAR)1 does not account for thrombin-driven obesity, so we explored the culprit role of PAR4 in this context. Male WT and PAR-4 -/- mice received a high fat diet (HFD) for 8 weeks, WT controls received standard chow. Body fat was quantified by NMR. Epididymal WAT was assessed by histology, immunohistochemistry, qPCR and lipase activity assay. 3T3-L1 preadipocytes were differentiated ± thrombin, acutely stimulated ± PAR4 activating peptide (AP) and assessed by immunoblot, qPCR and U937 monocyte adhesion. Epicardial adipose tissue (EAT) from obese and lean patients was assessed by immunoblot. PAR4 was upregulated in mouse WAT under HFD. PAR4 -/- mice developed less visceral adiposity and glucose intolerance under HFD, featuring smaller adipocytes, fewer macrophages and lower expression of adipogenic (leptin, PPARγ) and pro-inflammatory genes (CCL2, IL-1β) in WAT. HFD-modified activity and expression of lipases or perilipin were unaffected by PAR4 deletion. 3T3-L1 adipocytes differentiated with thrombin retained Ki67 expression, further upregulated IL-1β and CCL2 and were more adhesive for monocytes. In mature adipocytes, PAR4-AP increased phosphorylated ERK1/2 and AKT, upregulated Ki67, CCl2, IL-β and hyaluronan synthase 1 but not TNF-α mRNA, and augmented hyaluronidase-sensitive monocyte adhesion. Obese human EAT expressed more PAR4, CD68 and CD54 than lean EAT. PAR4 upregulated in obesity supports adipocyte hypertrophy, WAT expansion and thrombo-inflammation. The emerging PAR4 antagonists provide a therapeutic perspective in this context beyond their canonical antiplatelet action.

Stratigraphic and paleoceanographic alternations within a Mediterranean semi-enclosed, syn-rift basin during Marine Isotope Stage 5: The Gulf of Corinth, Greece - Spyros Sergiou; Maria Geraga; Sofia Pechlivanidou; Robert L. Gawthorpe; Ulysses Ninnemann; Anna-Nele Meckler; Sevasti Modestou; Dimitra Angelopoulou; Dimitra Antoniou; Paula Diz; Lisa McNeill; Donna J. Shillington; et al. (Marine Geology, 2024)

Datenanspruch und -verfügbarkeit für Vertiefte Überprüfungen an Stauanlagen im Vergleich von früher zu heute - Lisa-Maria Detert; Gabriele Demisch; Katja Last (WASSERWIRTSCHAFT, 2024)

Best practices, errors, and perspectives of half a century of plant translocation in Italy - Martina D'Agostino; Luigi Cao Pinna; Marta Carboni; Silvia Assini; Gianluigi Bacchetta; Fabrizio Bartolucci; Lisa Brancaleoni; Fabrizio Buldrini; Angelino Carta; Bruno Cerabolini; Roberta Maria Ceriani; Umberto Clementi; et al. (Conservation Biology, 2024)
Conservation translocations are becoming common conservation practice, so there is an increasing need to understand the drivers of plant translocation performance through reviews of cases at global and regional levels. The establishment of the Italian Database of Plant Translocation (IDPlanT) provides the opportunity to review the techniques used in 186 plant translocation cases performed in the last 50 years in the heart of the Mediterranean Biodiversity Hotspot. We described techniques and information available in IDPlanT and used these data to identify drivers of translocation outcomes. We tested the effect of 15 variables on survival of translocated propagules as of the last monitoring date with binomial logistic mixed‐effect models. Eleven variables significantly affected survival of transplants: life form, site protection, material source, number of source populations, propagation methods, propagule life stage, planting methods, habitat suitability assessment, site preparation, aftercare, and costs. The integration of vegetation studies in the selection of suitable planting sites significantly increased the success of translocation efforts. Although posttranslocation watering had a generally positive effect on translocation outcome, other aftercare techniques did not always increase transplant survival. Finally, we found that how funds were spent appeared to be more important than the actual amount spent. Plant translocations in Italy and in the Mediterranean area should account for the complexity of speciation, gene flow, and plant migrations that has led to local adaptations and has important implications for the choice and constitution of source material.

Sequential long-term optimization of shallow geothermal systems under descriptive uncertainty and dynamic variation of heating demand - Hesam Soltan Mohammadi; Lisa Maria Ringel; Michael de Paly; Peter Bayer (Geothermics, 2024)

Microplastics in gully pot sediment in urban areas: Presence, quantities and characteristics - Lisa Öborn; Heléne Österlund; Maria Viklander (Environmental Pollution, 2024)

Initial characterization of a transgenic mouse with overexpression of the human D1-dopamine receptor in the heart - Lina Maria Rayo Abella; Hannes Jacob; Christin Hesse; Britt Hofmann; Sarah Schneider; Lisa Schindler; Max Keller; Igor B. Buchwalow; CongYu Jin; Pertti Panula; Stefan Dhein; Jan Klimas; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Dopamine can exert effects in the mammalian heart via five different dopamine receptors. There is controversy whether dopamine receptors increase contractility in the human heart. Therefore, we have generated mice that overexpress the human D 1 -dopamine receptor in the heart (D 1 -TG) and hypothesized that dopamine increases force of contraction and beating rate compared to wild-type mice (WT). In D 1 -TG hearts, we ascertained the presence of D 1 -dopamine receptors by autoradiography using [ 3 H]SKF 38393. The mRNA for human D 1 -dopamine receptors was present in D 1 -TG hearts and absent in WT. We detected by in-situ-hybridization mRNA for D 1 -dopamine receptors in atrial and ventricular D 1 -TG cardiomyocytes compared to WT but also in human atrial preparations. We noted that in the presence of 10 µM propranolol (to antagonize β-adrenoceptors), dopamine alone and the D 1 - and D 5 -dopamine receptor agonist SKF 38393 (0.1–10 µM cumulatively applied) exerted concentration- and time-dependent positive inotropic effects and positive chronotropic effects in left or right atrial preparations from D 1 -TG. The positive inotropic effects of SKF 38393 in left atrial preparations from D 1 -TG led to an increased rate of relaxation and accompanied by and probably caused by an augmented phosphorylation state of the inhibitory subunit of troponin. In the presence of 0.4 µM propranolol, 1 µM dopamine could increase left ventricular force of contraction in isolated perfused hearts from D 1 -TG. In this model, we have demonstrated a positive inotropic and chronotropic effect of dopamine. Thus, in principle, the human D 1 -dopamine receptor can couple to contractility in the mammalian heart.

Forecasting potential invaders to prevent future biological invasions worldwide - Arman N. Pili; Boris Leroy; John G. Measey; Jules E. Farquhar; Adam Toomes; Phillip Cassey; Sebastian Chekunov; Matthias Grenié; Dylan van Winkel; Lisa Maria; Mae Lowe L. Diesmos; Arvin C. Diesmos; et al. (Global Change Biology, 2024)
The ever‐increasing and expanding globalisation of trade and transport underpins the escalating global problem of biological invasions. Developing biosecurity infrastructures is crucial to anticipate and prevent the transport and introduction of invasive alien species. Still, robust and defensible forecasts of potential invaders are rare, especially for species without known invasion history. Here, we aim to support decision‐making by developing a quantitative invasion risk assessment tool based on invasion syndromes (i.e., generalising typical attributes of invasive alien species). We implemented a workflow based on ‘Multiple Imputation with Chain Equation’ to estimate invasion syndromes from imputed datasets of species' life‐history and ecological traits and macroecological patterns. Importantly, our models disentangle the factors explaining (i) transport and introduction and (ii) establishment. We showcase our tool by modelling the invasion syndromes of 466 amphibians and reptile species with invasion history. Then, we project these models to amphibians and reptiles worldwide (16,236 species [c.76% global coverage]) to identify species with a risk of being unintentionally transported and introduced, and risk of establishing alien populations. Our invasion syndrome models showed high predictive accuracy with a good balance between specificity and generality. Unintentionally transported and introduced species tend to be common and thrive well in human‐disturbed habitats. In contrast, those with established alien populations tend to be large‐sized, are habitat generalists, thrive well in human‐disturbed habitats, and have large native geographic ranges. We forecast that 160 amphibians and reptiles without known invasion history could be unintentionally transported and introduced in the future. Among them, 57 species have a high risk of establishing alien populations. Our reliable, reproducible, transferable, statistically robust and scientifically defensible quantitative invasion risk assessment tool is a significant new addition to the suite of decision‐support tools needed for developing a future‐proof preventative biosecurity globally.

Proteomic features of gray matter layers and superficial white matter of the rhesus monkey neocortex: comparison of prefrontal area 46 and occipital area 17 - Paola B. Castro-Mendoza; Christina M. Weaver; Wayne Chang; Maria Medalla; Kathleen S. Rockland; Lisa Lowery; Elizabeth McDonough; Merina Varghese; Patrick R. Hof; Dan E. Meyer; Jennifer I. Luebke (Brain Structure and Function, 2024)
In this novel large-scale multiplexed immunofluorescence study we comprehensively characterized and compared layer-specific proteomic features within regions of interest of the widely divergent dorsolateral prefrontal cortex (A46) and primary visual cortex (A17) of adult rhesus monkeys. Twenty-eight markers were imaged in rounds of sequential staining, and their spatial distribution precisely quantified within gray matter layers and superficial white matter. Cells were classified as neurons, astrocytes, oligodendrocytes, microglia, or endothelial cells. The distribution of fibers and blood vessels were assessed by quantification of staining intensity across regions of interest. This method revealed multivariate similarities and differences between layers and areas. Protein expression in neurons was the strongest determinant of both laminar and regional differences, whereas protein expression in glia was more important for intra-areal laminar distinctions. Among specific results, we observed a lower glia-to-neuron ratio in A17 than in A46 and the pan-neuronal markers HuD and NeuN were differentially distributed in both brain areas with a lower intensity of NeuN in layers 4 and 5 of A17 compared to A46 and other A17 layers. Astrocytes and oligodendrocytes exhibited distinct marker-specific laminar distributions that differed between regions; notably, there was a high proportion of ALDH1L1-expressing astrocytes and of oligodendrocyte markers in layer 4 of A17. The many nuanced differences in protein expression between layers and regions observed here highlight the need for direct assessment of proteins, in addition to RNA expression, and set the stage for future protein-focused studies of these and other brain regions in normal and pathological conditions.

Testing a health baseline during a bivalve mollusc mortality event: An investigation into die-offs of pipi Paphies australis from Aotearoa New Zealand - Joanne Howells; Lisa Maria; Taryn Shirkey; Ari Carrington; Henry S. Lane (Journal of Invertebrate Pathology, 2024)

An international inter-laboratory study to compare digital PCR with ISO standardized qPCR assays for the detection of norovirus GI and GII in oyster tissue - Ingeborg L.A. Boxman; Ramia Molin; Sofia Persson; Anna Juréus; Claudia C.C. Jansen; Nils P. Sosef; Soizick F. Le Guyader; Joanna Ollivier; Maija Summa; Maria Hautaniemi; Elisabetta Suffredini; Simona Di Pasquale; et al. (Food Microbiology, 2024)

Aluminum and ABC transporter activity - Goezde Oezen; Lisa Kraus; Eva-Maria Schentarra; Jan Stephan Bolten; Joerg Huwyler; Gert Fricker (Environmental Toxicology and Pharmacology, 2024)

Development of dynamic sharing keys: Algorithms supporting management of renewable energy community and collective self consumption - Federico Gianaroli; Mattia Ricci; Paolo Sdringola; Maria Alessandra Ancona; Lisa Branchini; Francesco Melino (Energy and Buildings, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Methods for fungiform papillae assessment: A collaborative study among European research units - Maria Piochi; Sara Spinelli; Melania Melis; Monica Laureati; Emma Feeney; Lisa Methven; Qian Yang; Erminio Monteleone; Luisa Torri; Rebecca Ford; Ella Pagliarini; Iole Tomassini Barbarossa; et al. (Food Quality and Preference, 2024)

Perception of con- and heterospecific injury cues in tadpoles of dendrobatid, ranid and bufonid frogs (Anura) - Konrad Lipkowski; Diana Abondano Almeida; Lisa Maria Schulte (Evolutionary Ecology, 2024)
Predator-prey interactions are vital for organismal survival. They shape anti-predator mechanisms and often depend on sensory abilities. Tadpoles use chemical cues, such as injury cues (alarm cues), to assess predation risks and modify their life-history, morphology, and behaviours accordingly. However, the prevalence of chemically mediated anti-predator responses in species with distinct ecological niches (e.g. within phytotelmata) remains unknown, hindering our understanding of the ecological significance and evolution of alarm substances. Therefore, our study aimed to investigate chemically mediated anti-predator responses in tadpoles of two Neotropical poison dart frogs, Ranitomeya sirensis and Epipedobates anthonyi (and compare their responses to two Palearctic model organisms, Rana temporaria and Bufo bufo , which are known to utilise alarm substances). Through behavioural bioassays, we exposed predator-naïve tadpoles to extracts of each species (i.e. con- and heterospecific cues), including water as a control (i.e. five treatments per species). We assessed changes in their activity before and after stimulus introduction. Our results show that E. anthonyi did not respond to any of the stimuli, whereas R. sirensis displayed increased activity levels exclusively in response to conspecific cues, but not to heterospecific cues. With this, our findings suggest a specialized recognition system in R. sirensis , potentially directed at conspecific competitors but likely unrelated to anti-predator mechanisms. In contrast, E. anthonyi may be insensitive to injury cues or utilize alternative sensory modalities to respond to acute predation events. This study sheds light on the chemical alarm response system of Neotropical poison dart frog tadpoles, providing foundational understanding of how dendrobatids react to injury cues. It prompts questions about the ecological significance and evolutionary implications of chemical communication in species facing extreme resource limitation during development and underscores the importance of comparative research for understanding chemical communication in diverse aquatic ecosystems.

How do sea urchins prepare offspring to face ocean acidification? Gamete intraspecific differences and adaptability - Davide Asnicar; Lisa Locatello; Laura Zanovello; Riccardo Minichino; Luciano Masiero; Marco Munari; Maria Gabriella Marin (Frontiers in Marine Science, 2024)
Introduction Due to their relevant ecological position and well-studied biology, sea urchins are reference organisms for ocean acidification studies, at both within- and trans-generational levels. In this study, we examined gamete quality in specimens exposed to future predicted (-0.4 units) pH conditions during gametogenesis. Methods Egg physical characteristics, biochemical composition, and fatty acid profiles were assessed after two and six months of exposure, while sperm viability and velocity were analyzed after six months of exposure. Considering the documented intraspecific variability in response to ocean acidification, this study involved two populations of Paracentrotus lividus . One population was sampled from the highly variable lagoon of Venice (Site 1), while the other was obtained from a coastal area (Site 2) characterized by more stable environmental conditions and facing minimal anthropogenic stress. Results A different response was highlighted in the two sites. Noteworthy trends emerged, especially in the fatty acid profile and sperm traits. Although adults were fed the same diet, Site 1 eggs contained more high-energetic fatty acids than Site 2, potentially boosting the survival odds for the next generation. Moreover, Site 1 sperms displayed higher viability but slower motility compared to those from Site 2. Within sites, a significant difference between time points and a change in the fitness strategy of sea urchin females emerged when comparing eggs spawned after two and six months of exposure to reduced pH. The effects of time and exposure pH are more pronounced in animals from Site 1, suggesting a higher adaptability of this population rather than negative effects of ocean acidification. Discussion Overall, our findings suggest that sea urchins have the potential to acclimate to reduced pH and to produce gametes of the same quality as controls held at the currently natural pH. Our findings emphasize the relevance of combining investigations of gamete quality characteristics, particularly egg biochemistry and fatty acid composition, and considering site variability to fully understand the transgenerational response potential of sea urchins to ocean acidification.

Recent developments, challenges, and future research directions in tomographic characterization of fractured aquifers - Lisa Maria Ringel; Walter A. Illman; Peter Bayer (Journal of Hydrology, 2024)

Correction to: Ultra‑processed food consumption and nutritional frailty in older age - Roberta Zupo; Rossella Donghia; Fabio Castellana; Ilaria Bortone; Sara De Nucci; Annamaria Sila; Rossella Tatoli; Luisa Lampignano; Giancarlo Sborgia; Francesco Panza; Madia Lozupone; Giuseppe Colacicco; et al. (GeroScience, 2024)

Palaeoecological multiproxy reconstruction captures long-term climatic and anthropogenic impacts on vegetation dynamics in the Rhaetian Alps - Ilya Dziomber; Erika Gobet; Maria Leunda; Lisa Gurtner; Hendrik Vogel; Nicolas Tournier; Adrianus Damanik; Sönke Szidat; Willy Tinner; Christoph Schwörer (Review of Palaeobotany and Palynology, 2024)

Does fluoride exposure affect thyroid function? A systematic review and dose-response meta-analysis - Inga Iamandii; Lisa De Pasquale; Maria Edvige Giannone; Federica Veneri; Luigi Generali; Ugo Consolo; Linda S. Birnbaum; Jacqueline Castenmiller; Thorhallur I. Halldorsson; Tommaso Filippini; Marco Vinceti (Environmental Research, 2024)

The ethical assessment of Assisted Reproductive Technologies (ART) in wildlife conservation - Barbara de Mori; Elena Mercugliano; Pierfrancesco Biasetti; Ilaria Pollastri; Maria Michela Spiriti; Daniela Florio; Francesco Andreucci; Frank Göritz; Susanne Holtze; Cesare Galli; Jan Stejskal; Silvia Colleoni; et al. (Biological Conservation, 2024)

Diversification of refugia types needed to secure the future of coral reefs subject to climate change - Tim R. McClanahan; Emily S. Darling; Maria Beger; Helen E. Fox; Hedley S. Grantham; Stacy D. Jupiter; Cheryl A. Logan; Elizabeth Mcleod; Lisa C. McManus; Remy M. Oddenyo; Gautam S. Surya; Amelia. S. Wenger; et al. (Conservation Biology, 2024)
Identifying locations of refugia from the thermal stresses of climate change for coral reefs and better managing them is one of the key recommendations for climate change adaptation. We review and summarize approximately 30 years of applied research focused on identifying climate refugia to prioritize the conservation actions for coral reefs under rapid climate change. We found that currently proposed climate refugia and the locations predicted to avoid future coral losses are highly reliant on excess heat metrics, such as degree heating weeks. However, many existing alternative environmental, ecological, and life‐history variables could be used to identify other types of refugia that lead to the desired diversified portfolio for coral reef conservation. To improve conservation priorities for coral reefs, there is a need to evaluate and validate the predictions of climate refugia with long‐term field data on coral abundance, diversity, and functioning. There is also the need to identify and safeguard locations displaying resistance toprolonged exposure to heat waves and the ability to recover quickly after thermal exposure. We recommend using more metrics to identify a portfolio of potential refugia sites for coral reefs that can avoid, resist, and recover from exposure to high ocean temperatures and the consequences of climate change, thereby shifting past efforts focused on avoidance to a diversified risk‐spreading portfolio that can be used to improve strategic coral reef conservation in a rapidly warming climate.

A comparison of European surveillance programs for Campylobacter in broilers - Abbey Olsen; Silvia Bonardi; Lisa Barco; Marianne Sandberg; Nina Langkabel; Mati Roasto; Michał Majewski; Brigitte Brugger; Arja H. Kautto; Bojan Blagojevic; Joao B. Cota; Gunvor Elise Nagel-Alne; et al. (Food Control, 2024)

A review on inorganic gaseous pollutants in conservation spaces: monitoring instrumentation and indoor concentrations - Lisa Vergelli; Francesca Frasca; Chiara Bertolin; Gabriele Favero; Anna Maria Siani (Environmental Monitoring and Assessment, 2024)

Inputs, amplification and sinks of perfluoroalkyl substances at coastal Antarctica - Gemma Casas; Jon Iriarte; Lisa A. D'Agostino; Jose L. Roscales; Alicia Martinez-Varela; Maria Vila-Costa; Jonathan W. Martin; Begoña Jiménez; Jordi Dachs (Environmental Pollution, 2023)

Macroscopic sarcocystosis in a pig carcass from an Italian abattoir - Selene Rubiola; Linda Pasquariello; Felice Panebianco; Maria Teresa Capucchio; Elena Colombino; Federica Bordese; Enrique Giobbio; Lisa Fioriello; Silvia Braghin; Weronika Korpysa-Dzirba; Mirosław Różycki; Francesco Chiesa (Veterinary Research Communications, 2023)

DNA metabarcoding of cloacal swabs provides insight into diets of highly migratory sharks in the Mid‐Atlantic Bight - Jill A. Olin; Hidetoshi Urakawa; Michael G. Frisk; Alisa L. Newton; Maria Manz; Michael Fogg; Colin McMullen; Lisa Crawford; Oliver N. Shipley (Journal of Fish Biology, 2023)
The abundances of migratory shark species observed throughout the Mid‐Atlantic Bight (MAB) during productive summer months suggest that this region provides critical habitat and prey resources to these taxa. However, the principal prey assemblages sustaining migratory shark biomass in this region are poorly defined. We applied high‐throughput DNA metabarcoding to shark feces derived from cloacal swabs across nine species of Carcharhinid and Lamnid sharks to (1) quantify the contribution of broad taxa (e.g., invertebrates, fishes) supporting shark biomass during seasonal residency in the MAB and (2) determine whether the species displayed distinct dietary preference indicative of resource partitioning. DNA metabarcoding resulted in high taxonomic (species‐level) resolution of shark diets with actinopterygian and elasmobranch fishes as the dominant prey categories across the species. DNA metabarcoding identified several key prey groups consistent across shark taxa that are likely integral for sustaining their biomass in this region, including Atlantic menhaden ( Brevoortia tyrannus ), Atlantic mackerel ( Scomber scombrus ), and benthic elasmobranchs, including skates. Our results are consistent with previously published stomach content data for the shark species of similar size range in the Northwest Atlantic Ocean, supporting the efficacy of cloacal swab DNA metabarcoding as a minimally invasive diet reconstruction technique. The high reliance of several shark species on Atlantic menhaden could imply wasp‐waist food‐web conditions during the summer months, whereby high abundances of forage fishes sustain a diverse suite of migratory sharks within a complex, seasonal food web.

A recipe for plastic: Expert insights on plastic additives in the marine environment - Thomas Maes; Fiona Preston-Whyte; Stephanie Lavelle; Alessio Gomiero; Andy M. Booth; Maria Jesus Belzunce-Segarra; Juan Bellas; Steven Brooks; Adil Bakir; Lisa I. Devriese; Christopher Kim Pham; Bavo De Witte (Marine Pollution Bulletin, 2023)

Design of a national patient-centred clinical pathway for sepsis in Sweden - Kristoffer Strålin; Adam Linder; Magnus Brink; Patrik Benjaminsson-Nyberg; Jesper Svefors; Maria Bengtsson-Toni; Christina Abelson; Karsten Offenbartl; Kristina Björkqvist; Mari Rosenqvist; Annica Rönnkvist; Jenny Svärd-Backlund; et al. (Infectious Diseases, 2023)

Status and Management of Mixed Fisheries: A Global Synthesis - Ming Sun; Yunzhou Li; Lisa Suatoni; Alexander Kempf; Marc Taylor; Elizabeth Fulton; Cody Szuwalski; Maria Teresa Spedicato; Yong Chen (Reviews in Fisheries Science & Aquaculture, 2023)

Fetal growth at term and placental oxidative stress in a tissue micro-array model: a histological and immunohistochemistry study - Serena Xodo; Lisa Celante; Stefania Liviero; Maria Orsaria; Laura Mariuzzi; Matteo De Luca; Giuseppe Damante; Lorenza Driul; Angelo Cagnacci; Annalisa Ferino; Eros Di Giorgio; Luigi Xodo; et al. (Histochemistry and Cell Biology, 2023)
This study examines 8-hydroxyguanine (8-oxo-Gua) staining in placental tissue samples based on fetal size at birth as well as its relationships with placental histology and other pregnancy variables. This prospective cohort study included women > 18 years with a singleton pregnancy, a live fetus, fluency in Italian, and delivery at term. A total of 165 pregnancies were included in the study. The nuclear syncytiotrophoblast 8-oxo-Gua staining score in LGA was substantially greater than in late FGR ( p < 0.05), although the cytoplasm score was lower in SGA and LGA than in AGA ( p < 0.05). Furthermore, a sex-specific pattern of 8-oxo-Gua staining was discovered in single-term placentas, with more oxidative damage found in the nuclei of syncytiotrophoblast cells and stromal and endothelial cells in AGA males compared to AGA females ( p < 0.05). Second, the histological pattern of late FGR placentae differed by gender. Finally, a significant correlation ( p < 0.05) was found between high-intensity 8-oxo-Gua staining in the cytoplasm of syncytiotrophoblast cells and thrombi in the chorionic plate or villi in males. On the other hand, female fetuses demonstrated a significant connection ( p < 0.05) between high-intensity 8-oxo-Gua staining in endothelial and stromal cells and high birthweight MoM values. Our findings indicated a significant variation in the oxidative stress pattern between male and female placentae, implying that fetal growth is regulated differently in the two sexes.

Exploring S-RNase diversity in the Andean black cherry (Prunus serotina) using MinION sequencing: a cost-effective approach with increased genotyping resolution - Mónica Becerra-Wong; Milton Gordillo-Romero; Lisa C. Baus; Martín Terán-Velástegui; Maria de Lourdes Torres; Andres F. Torres (Euphytica, 2023)

Low progesterone concentration in early pregnancy is detrimental to conceptus development and pregnancy outcome in horses - Lisa-Hélène Wagner; Jörg Aurich; Maria Melchert; Carolina T.C. Okada; Camille Gautier; Martim Kaps; Svenja Claaßen; Christine Aurich (Animal Reproduction Science, 2023)

Plasma concentrations of per- and polyfluoroalkyl substances in pregnancy and breastfeeding duration in Project Viva - Lisa B. Rokoff; Jordyn T. Wallenborn; Maria H. Harris; Sheryl L. Rifas-Shiman; Rachel Criswell; Megan E. Romano; Jessica G. Young; Antonia M. Calafat; Emily Oken; Sharon K. Sagiv; Abby F. Fleisch (Science of The Total Environment, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Unexpected finding of a rare pathogenic germline BRCA1 variant in an intrahepatic cholangiocarcinoma using the Oncomine Focus DNA assay: clinical and diagnostic implications - Maria De Bonis; Francesco Mannavola; Lisa Salvatore; Elisa De Paolis; Camilla Nero; Luciano Giacò; Giampaolo Tortora; Felice Giuliante; Andrea Urbani; Giovanni Scambia; Nicola Normanno; Angelo Minucci (Molecular Biology Reports, 2023)

Effects of sub-physiological plasma progesterone concentration in the early luteal phase on embryonic and fetal development, pregnancy outcome and foal characteristics - Lisa-Hélène Wagner; Maria Melchert; Carolina Tiemi Cardoso Okada; Martim Kaps; Svenja Claaßen; Christine Aurich (Journal of Equine Veterinary Science, 2023)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

The Asymmetric Response Concept explains ecological consequences of multiple stressor exposure and release - Matthijs Vos; Daniel Hering; Mark O. Gessner; Florian Leese; Ralf B. Schäfer; Ralph Tollrian; Jens Boenigk; Peter Haase; Rainer Meckenstock; Daria Baikova; Helena Bayat; Arne Beermann; et al. (Science of The Total Environment, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

Effect of optic flow on spatial updating: insight from an immersive virtual reality study - Lisa Cardelli; Maria Giulia Tullo; Gaspare Galati; Valentina Sulpizio (Experimental Brain Research, 2023)

Microtextural signatures in quartz grains and foraminifera from tsunami deposits of the Portuguese shelf - Missilene Yhasnara; Pedro J. M. Costa; Francisco Dourado; Maria Virginia Alves Martins; Lisa Feist; Piero Bellanova; Klaus Reicherter (Geo-Marine Letters, 2023)

The invasion history of Elodea canadensis and E. nuttallii (Hydrocharitaceae) in Italy from herbarium accessions, field records and historical literature - Fabrizio Buldrini; Giovanna Pezzi; Martina Barbero; Alessandro Alessandrini; Lucia Amadei; Sebastiano Andreatta; Nicola Maria Giuseppe Ardenghi; Stefano Armiraglio; Simonetta Bagella; Rossano Bolpagni; Ilaria Bonini; Daniela Bouvet; et al. (Biological Invasions, 2023)
We analysed the invasion history of two North American macrophytes ( Elodea canadensis and E. nuttallii ) in Italy, through an accurate census of all available herbarium and field records, dating between 1850 and 2019, and a rich literature collection describing the initial introduction and naturalisation phase that supports the results obtained by the occurrence records. Elodea canadensis arrived in Italy before 1866 and had two invasion phases, between the 1890s and 1920s and between the 1990s and 2000s; E. nuttallii , probably arrived in the 1970s, started invading in 2000 and the invasion is still ongoing. Botanical gardens and fish farming played a crucial role in dispersal and naturalisation of both species. The current invasion range of both species is centred in northern Italy, with scattered occurrences of E. canadensis in central and southern regions. River Po represents a dispersal barrier to the Mediterranean region and a strategic monitoring site to prevent the invasion in the peninsula. The study detects differences in the niches of the two species during the introduction and naturalisation phase and a habitat switch occurred after 1980 in E. canadensis and after 2000 in E. nuttallii , during their expansion phases. For E. canadensis the switch corresponds to the second invasion round. Further research can clarify whether the second invasion round is due to confusion of the recently introduced E. nuttallii with E. canadensis , to a cryptic introduction of a new genotype, to post-introduction evolution, or just to an increased scientific interest in biological invasions.

Ultra-processed food consumption and nutritional frailty in older age - Roberta Zupo; Rossella Donghia; Fabio Castellana; Ilaria Bortone; Sara De Nucci; Annamaria Sila; Rossella Tatoli; Luisa Lampignano; Giancarlo Sborgia; Francesco Panza; Madia Lozupone; Giuseppe Colacicco; et al. (GeroScience, 2023)
Frailty is a multidisciplinary public health issue and nutrition is key concern. Given the scientific consistency about inflammation as shared pathway to poor nutrition and frailty, food processing seems a suitable target to gain evidence in frailty prevention nutrition settings. This study aimed to assess diet in relation to nutritional frailty using the NOVA classification. Browsing the dataset of the Salus in Apulia, 2185 older adults were found to have completed the nutritional assessment, providing eligible data for this study goal. A validated construct, based on the co-presence of physical frailty by CHS criteria plus nutritional imbalance, was applied to characterize nutritional frailty phenotypes. Using the NOVA classification, daily food and beverage intakes from an 85-item self-administered FFQ were assigned to three categories, and effect sizes were tested among groups according to nutritional frailty status (presence/absence). Raw and adjusted logistic regression models were run to assess associations between NOVA food categories by quintiles of daily exposure (very-low, low, mild, moderate, high) and nutritional frailty. Nutritional frailty prevalence was 27%, being more frequent in males. Eating more unprocessed or minimally processed foods was inversely related to nutritional frailty, even after adjustment (OR: 0.10, 95%CI 0.07–0.16), showing a downward ORs behavior toward lower consumption quintiles. Listing in the quintile of moderate consumption of processed foods meant a nearly 50% increase in nutritional frailty probability (OR: 1.46, 95%CI 1.03–2.06), while the probability was double for the highest quintile against the lowest (OR: 3.22, 95%CI 2.27–4.58). A growing probability of nutritional frailty was found for increasing consumption of ultra-processed foods, but significance was lacking. The contribution of food processing to poor nutrition needs to be considered when promoting a better understanding of effective nutritional screening in aging. Therefore, food processing should be accounted for when composing diet guidelines for the older population within the framework of multidisciplinary efforts to ease the frailty healthcare burden.

Modelling extraction kinetics of betalains from freeze dried beetroot powder into aqueous ethanol solutions - Rahul Kumar; Maria Jose Oruna-Concha; Lisa Methven; Keshavan Niranjan (Journal of Food Engineering, 2023)

Application of transcriptome profiling to inquire into the mechanism of nanoplastics toxicity during Ciona robusta embryogenesis - Maria Concetta Eliso; Elisa Bergami; Lisa Bonciani; Roberto Riccio; Giulia Belli; Mattia Belli; Ilaria Corsi; Antonietta Spagnuolo (Environmental Pollution, 2023)

The escalating global problem of accidental human-mediated transport of alien species: A case study using alien herpetofauna interceptions in New Zealand - Arman N. Pili; Reid Tingley; Dylan van Winkel; Lisa Maria; David G. Chapple (Biological Conservation, 2023)

Synthesis, structural characterization and study of antioxidant and anti-PrPSc properties of flavonoids and their rhenium(I)–tricarbonyl complexes - Pigi Glykofridi; Vassiliki-Eleni Tziouri; Konstantinos Xanthopoulos; Maria-Eirini Vlachou; Susana Correia; Anna-Lisa Fischer; Katrin Thüne; Antonios Hatzidimitriou; Inga Zerr; Matthias Schmitz; Theodoros Sklaviadis; Dimitra Hadjipavlou-Litina; et al. (JBIC Journal of Biological Inorganic Chemistry, 2023)
This study aims at the synthesis and initial biological evaluation of novel rhenium–tricarbonyl complexes of 3,3′,4′,5,7-pentahydroxyflavone (quercetin), 3,7,4΄-trihydroxyflavone (resokaempferol), 5,7-dihydroxyflavone (chrysin) and 4΄,5,7-trihydroxyflavonone (naringenin) as neuroprotective and anti-PrP agents. Resokaempferol was synthesized from 2,2΄,4-trihydroxychalcone by H 2 O 2 /NaOH. The rhenium–tricarbonyl complexes of the type fac -[Re(CO) 3 (Fl)(sol)] were synthesized by reacting the precursor fac -[Re(CO) 3 (sol) 3 ] + with an equimolar amount of the flavonoids (Fl) quercetin, resokaempferol, chrysin and naringenin and the solvent (sol) was methanol or water. The respective Re–flavonoid complexes were purified by semi-preparative HPLC and characterized by spectroscopic methods. Furthermore, the structure of Re–chrysin was elucidated by X-ray crystallography. Initial screening of the neuroprotective properties of these compounds included the in vitro assessment of the antioxidant properties by the DPPH assay as well as the anti-lipid peroxidation of linoleic acid in the presence of AAPH and their ability to inhibit soybean lipoxygenase. From the above studies, it was concluded that the complexes’ properties are mainly correlated with the structural characteristics and the presence of the flavonoids. The flavonoids and their respective Re-complexes were also tested in vitro for their ability to inhibit the formation and aggregation of the amyloid-like abnormal prion protein, PrP Sc , by employing the real-time quaking-induced conversion assay with recombinant PrP seeded with cerebrospinal fluid from patients with Creutzfeldt–Jakob disease. All the compounds blocked de novo abnormal PrP formation and aggregation. Graphical abstract

Interpreting biomonitoring data: Introducing the international human biomonitoring (i-HBM) working group's health-based guidance value (HB2GV) dashboard - Shoji F. Nakayama; Annie St-Amand; Tyler Pollock; Petra Apel; Yu Ait Bamai; Dana Boyd Barr; Jos Bessems; Antonia M. Calafat; Argelia Castaño; Adrian Covaci; Radu Corneliu Duca; Sarah Faure; et al. (International Journal of Hygiene and Environmental Health, 2023)

Otoliths of marine fishes record evidence of low oxygen, temperature and pH conditions of deep Oxygen Minimum Zones - Leticia Maria Cavole; Karin E. Limburg; Natalya D. Gallo; Anne Gro Vea Salvanes; Arturo Ramírez-Valdez; Lisa A. Levin; Octavio Aburto Oropeza; Andreas Hertwig; Ming-Chang Liu; Kevin D. McKeegan (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Review of Environmental Monitoring by Means of Radio Waves in the Polar Regions: From Atmosphere to Geospace - Lucilla Alfonsi; Nicolas Bergeot; Pierre J. Cilliers; Giorgiana De Franceschi; Lisa Baddeley; Emilia Correia; Domenico Di Mauro; Carl-Fredrik Enell; Mark Engebretson; Reza Ghoddousi-Fard; Ingemar Häggström; Young-bae Ham; et al. (Surveys in Geophysics, 2022)
The Antarctic and Arctic regions are Earth's open windows to outer space. They provide unique opportunities for investigating the troposphere–thermosphere–ionosphere–plasmasphere system at high latitudes, which is not as well understood as the mid- and low-latitude regions mainly due to the paucity of experimental observations. In addition, different neutral and ionised atmospheric layers at high latitudes are much more variable compared to lower latitudes, and their variability is due to mechanisms not yet fully understood. Fortunately, in this new millennium the observing infrastructure in Antarctica and the Arctic has been growing, thus providing scientists with new opportunities to advance our knowledge on the polar atmosphere and geospace. This review shows that it is of paramount importance to perform integrated, multi-disciplinary research, making use of long-term multi-instrument observations combined with ad hoc measurement campaigns to improve our capability of investigating atmospheric dynamics in the polar regions from the troposphere up to the plasmasphere, as well as the coupling between atmospheric layers. Starting from the state of the art of understanding the polar atmosphere, our survey outlines the roadmap for enhancing scientific investigation of its physical mechanisms and dynamics through the full exploitation of the available infrastructures for radio-based environmental monitoring.

The Impact of an Unconventional Elective in Narrative Medicine and Pediatric Psycho-oncology on Humanism in Medical Students - F. Jeffrey Lorenz; Matthew C. Darok; Lisa Ho; Maria S. Holstrom-Mercader; Andrew S. Freiberg; Cheryl A. Dellasega (Journal of Cancer Education, 2022)

Cryopreservation of human amniotic membrane for ocular surface reconstruction: a comparison between protocols - Mattia Lamon; Marina Bertolin; Diletta Trojan; Lisa Spagnol; Pietro Maria Donisi; Davide Camposampiero; Diego Ponzin; Stefano Ferrari (Cell and Tissue Banking, 2022)

Regional Characterization of the Gottingen Minipig Brain by [18 F]FDG Dynamic Pet Modeling - Santarelli Maria Filomena; Pasini Elena; Baroni Carlotta; De Santi Lisa Anita; Furini Giulia; Terlizzi Domiziana; Cavaleri Samuele; Bertasi Michelangelo; Grasso Enrico; Genovesi Dario; Positano Vincenzo; Lionetti Vincenzo; et al. (Journal of Medical and Biological Engineering, 2022)
Purpose To determine the best kinetic model to be applied on dynamic brain [ 18 F]FDG PET images by characterizing the regional brain glucose metabolism of normal Göttingen minipigs. Methods Nine Göttingen minipigs were scanned with a clinical PET/CT tomograph, starting from the injection of an intravenous bolus of [ 18 F]FDG, for about 25 min. Dynamic images were reconstructed and nine brain regions of interest (ROI), plus a vascular region, were defined and time-activity curves (TAC) were determined. Three kinetic models were considered for fitting with experimental TACs: one-tissue compartment model 1TC, two-tissue irreversible compartment model 2TCi and two-tissue reversible model 2TC. Akaike Information Criterion was considered to evaluate the goodness of each model fitting. Regional and global kinetic parameter values were evaluated, in addition to the partition coefficient, net influx rate and retention index (RI). Results Both 2TCi and 2TC models turned out to be good choices for the next analysis. Parameter values were very similar between the different brain regions, with similar values to when the brain as a whole is considered (kinetic parameters mean values, from 2TCi model: K 1 = 1.0 ml/g/min, k 2 = 0.49 min − 1 , k 3 = 0.034 min − 1 , K 1 /k 2 = 2.14ml/g, K i =0.069 ml/g/min; from 2TC model: K 1 = 1.10 ml/g/min, k 2 = 0.54 min − 1 , k 3 = 0.058 min − 1 , k 4 = 0.039 min − 1 , K 1 /k 2 = 2.18 ml/g, K i = 0.10 ml/g/min; RI mean ± sd: 0.147 ± 0.037 min − 1 ), with the exception of the cerebellum (mean values from the 2TCi model: K 1 = 0.52 ml/g/min, k 2 = 0.56 min − 1 , k 3 = 0.025 min − 1 , K 1 /k 2 = 0.98ml/g, K i = 0.022 ml/g/min; from 2TC model: K 1 = 0.54 ml/g/min, k 2 = 0.61 min − 1 , k 3 = 0.044 min − 1 , k 4 = 0.038 min − 1 , K 1 /k 2 = 0.95ml/g, K i =0.032 ml/g/min; RI mean ± sd: 0.071 ± 0.018 min − 1 ). Conclusion The two-tissue model is able to describe the regional brain metabolism in Göttingen minipigs. Compared to the 2TCi model, in the 2TC model the k 4 micro-parameter was also evaluated. This led to adjustments of the other microparameters, especially k 3 and consequently the net influx rate K i . For healthy minipigs, the glucose metabolism was similar in all of the brain regions analyzed, with the exception of the cerebellum, where the FDG uptake was lower.

Manipulation of phyllosphere bacterial communities reversibly alters the plant microbiome and leaf traits in the field - Lisa-Maria Ohler; Sarah Seeleitner; Stefan Haselberger; Sabine Kraushaar; Jan-Christoph Otto; Birgit Mitter; Robert R. Junker (Alpine Botany, 2022)
Bacterial communities in the phyllosphere are shaped by host genotype and phenotype and spatio-temporal variation of the environment. In turn, bacteria have the potential for altering the plant phenotype. Field experiments can help to estimate bacterial effects on plant functional traits under natural conditions. We used a transplantation approach of culturable bacterial communities to explore how manipulation of leaf-associated microbial communities in two different successional stages within a glacier foreland can influence microbial composition and functional plant traits. Our study documents successional stage-specific variations in the composition of foliar bacterial communities and shifts therein throughout a season and between years. We show that cultured bacteria transferred between plant communities can alter diversity and composition of the microbiome on plant community level as well as species-specific functional plant traits of two selected plant species within one growing season. Furthermore, our results demonstrate a strong resilience of plant-associated bacterial communities and of plants in response to bacterial invaders. Our study illustrates that inoculation experiments in the field with naturally occurring microbial communities of wild plants are suited to investigate complex interactions between microbial communities, the environment, and plant traits.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Two degrees and the SDGs: a network analysis of the interlinkages between transnational climate actions and the Sustainable Development Goals - Johanna Coenen; Lisa-Maria Glass; Lisa Sanderink (Sustainability Science, 2022)
Given the interconnectedness of climate change and sustainable development, policymakers and scholars have started to investigate how climate actions can contribute to achieving the Sustainable Development Goals (SDGs), and vice versa. To date, research has mainly focused on the national and international levels, while little is known about the interlinkages between climate actions and the SDGs at the transnational level. Not only nation states, but also non-state actors undertake ambitious actions designed to reduce greenhouse gas emissions and to promote sustainable development. Using content analysis and network analysis techniques, we examine the interlinkages between the climate actions of 72 transnational initiatives and the 169 targets of the 17 SDGs. We find that actions of 71 initiatives contribute to achieving 16 SDGs, thus generating valuable co-benefits. Besides SDG 13 on climate action and SDG 17 on partnerships for the goals, transnational climate actions frequently address SDGs 9 on industry, innovation and infrastructure, SDG 7 on affordable and clean energy, and SDG 12 on responsible consumption and production. While SDG 3 on good health and well-being and SDG 4 on quality education are barely addressed, SDG 5 on gender equality is not at all covered by transnational climate actions. Additionally, the network reveals that SDG 9 is highly synergistic with many other frequently addressed SDGs and functions as an important connector between them. Finally, our results indicate that transnational initiatives fill a governance gap left by states with regards to SDG 12. Climate initiatives of non-state actors can thus complement state-led actions to implement the Paris Agreement and the SDGs jointly.

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

The value of lamp to rule out imported malaria diagnosis: a retrospective observational study in Milan, Italy - Andrea Giacomelli; Maria Elena Monti; Romualdo Grande; Letizia Oreni; Laura Galimberti; Anna Lisa Ridolfo; Cecilia Bonazzetti; Federico Sabaini; Laura Cordier; Agostino Zambelli; Giuliano Rizzardini; Massimo Galli; et al. (Infectious Diseases, 2022)

Genetic resistance to Campylobacter coli and Campylobacter jejuni in wild boar (Sus scrofa L.) - Francesca Cecchi; Maria Chiara Fabbri; Lara Tinacci; Roberta Nuvoloni; Francesca Marotta; Lisa Di Marcantonio; Giovanni Cilia; Fabio Macchioni; Andrea Armani; Filippo Fratini; Francesca Pedonese (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)
We studied the genetic resistance to Campylobacter coli and Campylobacter jejuni in wild boar using both STR analysis and genome-wide association studies (GWAS). A total of 60 wild boars hunted in Tuscany (Italy) during the 2018/2019 hunting season were analyzed and genotyped. During postmortem operations, fecal swabs, liver samples and kidneys were collected. Two groups of animals were considered for the statistical analysis: 28 Campylobacter positive (22 for C. coli and 6 for C. jejuni ) and 32 Campylobacter negative. Regarding STR analysis, 15 markers belonging to a marker panel validated by the International Society of Animal Genetics (ISAG) for swine were used: for each marker, alleles and genotype frequencies between the two groups of animals were compared using the Chi-square test and Fisher’s exact tests. To analyze the genetic variability within groups, the following parameters were computed: molecular coancestry coefficients (fij), kinship distance (Dk), inbreeding coefficient (Fi), and genetic similarities (GS). The internal relatedness (IR) was also calculated, and ANOVA was used to verify the relationships between IR and Campylobacter groups. For GWAS, the Geneseek Genomic Profiler Porcine HD (70 k), containing 62,330 SNPs, was used. No differences in the internal relatedness (IR) were observed between the two groups ( F = 5.64, P = 0.065) and no significant association between STRs and SNPs and Campylobacter positivity was observed. Although genetic resistance to bacterial diseases is often regulated by multiple genes controlling different processes of the host–pathogen interaction, in our studies no candidate genes that could be directly or indirectly involved in the development of the disease were identified.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Streptococcus pneumoniae colonization in health care professionals at a tertiary university pediatric hospital - Lisa-Maria Steurer; Mathias Hetzmannseder; Birgit Willinger; Peter Starzengruber; Claudia Mikula-Pratschke; Andrea Kormann-Klement; Michael Weber; Angelika Berger; Agnes Grill (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Streptococcus pneumoniae is a commensal of the human upper respiratory tract. In certain cases, it can lead to serious invasive infections peaking in very young children and the elderly. Especially young children are frequent carriers and are thus regarded as the reservoir for horizontal transmission of pneumococci. This is the first study evaluating pneumococcal colonization patterns in healthcare professionals working in a tertiary care pediatric hospital, including carriage prevalence, serotype distribution, and risk factors for carriage. One oropharyngeal and one nasal swab per individual were directly plated onto appropriate agar plates and conventional culture was used for bacterial identification. Pneumococcal isolates underwent serotyping using Neufeld’s Quellung reaction with type-specific antisera. Additional nasal and oropharyngeal swabs were taken for qPCR analysis targeting lytA . In total, 437 individuals were enrolled. S. pneumoniae was isolated in 4.8% (21/437) of the study cohort using conventional culture and in 20.1% (88/437) of subjects using qPCR. Independent risk factors for pneumococcal carriage were living in the same household with children under 8 years of age and being aged 36–45 years with a carriage prevalence reaching 11.6% (vs. 2.9%, p = 0.002) and 6.7% (vs. 4.3%, p = 0.029), respectively. The most common serotypes were 6C and 3. A total of 71.4% (15/21) of the detected serotypes are not included in any currently available pneumococcal vaccine; 28.6% (6/21) of the carried serotypes are included in the PCV13 vaccine. We found a relevant amount of pneumococcal carriage bearing the potential risk of horizontal in-hospital transmission.

Bioerosion features of boring polydorid polychaetes in the North Adriatic Sea - Torcuato Pulido Mantas; Lisa Pola; Carlo Cerrano; Maria Cristina Gambi; Barbara Calcinai (Hydrobiologia, 2022)
Considering the pivotal role played by erosive organisms in the marine habitat and the scanty knowledge of this phenomenon in the Mediterranean Sea, the present study aimed to identify the pioneer excavating organisms occurring in the first stages of bioerosion, providing the first estimation of their rate of erosion along the North Adriatic Sea. Bioerosion activity was investigated by deploying sets of limestone panels for a period of 2 years. Moreover, micro-computed tomography was used for the first time to study polychaete erosion, confirming it is a very useful tool for the description of erosion processes. Blocks were placed in the touristic harbor Marina Dorica (Ancona) in July 2017 and periodically collected, the first time after a 6-month period, then bimonthly. Two species of the polychaete genus Polydora were the only boring organisms that settled on the experimental substrates. Erosion rate was estimated by measuring the holes produced by both worm species, and the eroded volumes obtained by resin casts of the holes. Polydora appeared after 6 months of exposure significantly changing its density rates (holes·100 cm −2 ·month −1 ) during the exposure, being comparable with densities reported from tropical areas. The erosion rate on the contrary is lower, reaching values of 0.053 g·cm −2 ·year −1 .

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The canine counts! Significance of a craniodental measure to describe sexual dimorphism in canids: Golden jackals (Canis aureus) and African wolves (Canis lupaster) - Jennifer Hatlauf; Lisa Maria Krendl; Johannes Tintner; Paul Griesberger; Miklós Heltai; Georgi Markov; Suvi Viranta; Klaus Hackländer (Mammalian Biology, 2021)
Sexual dimorphism is a widespread phenomenon among mammals, including carnivorans. While sexual dimorphism in golden jackals ( Canis aureus ) has been analysed in the past, in the related and apparently convergent canid, the African wolf ( Canis lupaster ), it is poorly studied and showed to be relatively small. Previously, sexual size dimorphism (SSD) research in these species was mostly based on skull and body measurements. In our study, we also included dental measurements, namely the diameter of the canine. We used 11 measured sections of 104 adult specimens, comprising 61 golden jackal and 43 African wolf skulls. Data analyses were carried out through logistic regression and conditional inference trees (CIT). To compare the results of SSD to other species, sexual dimorphism indices (SDI) were calculated. Golden jackals and African wolves show significant sexual size dimorphism, both in cranial and dental size. The logistic regression revealed that the mesiodistal diameter of the upper canine is most effective in discerning the sexes. The difference in the calculated SDI of the canine diameter between the sexes amounted to 8.71 in golden jackals and 14.11 in African wolves, respectively—with regional diversity. Thus, the canine diameter is an important measure to investigate SSD as well as an easy tool to apply in the field.

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Potential application and beneficial effects of a marine microalgal biomass produced in a high-rate algal pond (HRAP) in diets of European sea bass, Dicentrarchus labrax - Giulia Pascon; Maria Messina; Lisa Petit; Luisa Maria Pinheiro Valente; Beatriz Oliveira; Cyrille Przybyla; Gilbert Dutto; Francesca Tulli (Environmental Science and Pollution Research, 2021)
Microalgae have been used as live food in aquatic species. In recent years, the interest in microalgae has considerably increased, thanks to the evolution of production techniques that have identified them as an ecologically attractive aquafeed ingredient. The present study provides the first data about the effects of dietary inclusion of a microalgae consortium grown in a high-rate algal pond system on zootechnical performance, morphometric indices, and dietary nutrient digestibility as well as morphology and functionality of the digestive system of European sea bass, Dicentrarchus labrax . A dietary treatment including a commercial mono-cultured microalgae ( Nannochloropsis sp.) biomass was used for comparison. Six hundred and thirty-six European sea bass juveniles (18 ± 0.28 g) were randomly allotted into 12 experimental groups and fed 4 different diets for 10 weeks: a control diet based on fish meal, fish oil, and plant protein sources; a diet including 10% of Nannochloropsis spp. biomass (100 g/kg diet); and two diets including two levels (10% and 20%) of the microalgal consortium (100 and 200 g/kg diet) . Even at the highest dietary inclusion level, the microalgal consortium (200 g/kg diet) did not affect feed palatability and fish growth performance. A significant decrease in the apparent digestibility of dry matter, protein, and energy was observed in diets including 10 and 20% of the microalgal consortium, but all fish exhibited a well-preserved intestinal histomorphology. Moreover, dietary inclusion with the microalgal consortium significantly increased the enzymatic activity of maltase, sucrase-isomaltase, and ɤ-glutamil transpeptidase in the distal intestine of the treated European sea bass. Algal consortium grown using fish farm effluents represents an attempt to enhance the utilization of natural biomasses in aquafeeds when used at 10 % as substitute of vegetable ingredients in diet for European sea bass.

Establishing the Foundation for the Global Observing System for Marine Life - Erin V. Satterthwaite; Nicholas J. Bax; Patricia Miloslavich; Lavenia Ratnarajah; Gabrielle Canonico; Daniel Dunn; Samantha E. Simmons; Roxanne J. Carini; Karen Evans; Valerie Allain; Ward Appeltans; Sonia Batten; et al. (Frontiers in Marine Science, 2021)
Maintaining healthy, productive ecosystems in the face of pervasive and accelerating human impacts including climate change requires globally coordinated and sustained observations of marine biodiversity. Global coordination is predicated on an understanding of the scope and capacity of existing monitoring programs, and the extent to which they use standardized, interoperable practices for data management. Global coordination also requires identification of gaps in spatial and ecosystem coverage, and how these gaps correspond to management priorities and information needs. We undertook such an assessment by conducting an audit and gap analysis from global databases and structured surveys of experts. Of 371 survey respondents, 203 active, long-term (>5 years) observing programs systematically sampled marine life. These programs spanned about 7% of the ocean surface area, mostly concentrated in coastal regions of the United States, Canada, Europe, and Australia. Seagrasses, mangroves, hard corals, and macroalgae were sampled in 6% of the entire global coastal zone. Two-thirds of all observing programs offered accessible data, but methods and conditions for access were highly variable. Our assessment indicates that the global observing system is largely uncoordinated which results in a failure to deliver critical information required for informed decision-making such as, status and trends, for the conservation and sustainability of marine ecosystems and provision of ecosystem services. Based on our study, we suggest four key steps that can increase the sustainability, connectivity and spatial coverage of biological Essential Ocean Variables in the global ocean: (1) sustaining existing observing programs and encouraging coordination among these; (2) continuing to strive for data strategies that follow FAIR principles (findable, accessible, interoperable, and reusable); (3) utilizing existing ocean observing platforms and enhancing support to expand observing along coasts of developing countries, in deep ocean basins, and near the poles; and (4) targeting capacity building efforts. Following these suggestions could help create a coordinated marine biodiversity observing system enabling ecological forecasting and better planning for a sustainable use of ocean resources.

Coexistence of rice production and threatened plant species: testing Marsilea quadrifolia L. in N-Italy - Anna Corli; Simone Orsenigo; Renato Gerdol; Stefano Bocchi; Alfons P. Smolders; Lisa Brancaleoni; Maria Teresa Caffi; Thomas Abeli; Graziano Rossi (Paddy and Water Environment, 2021)
In the past, the aquatic pteridophyte Marsilea quadrifolia L. was considered as a weed in paddy fields of southern Europe. The systematic use of herbicides as a crucial component of intensive agronomic approach has led to a dramatic decline in M. quadrifolia populations in European countries, mostly in the Mediterranean area. However, the introduction in recent years of sustainable rice cultivation practices has allowed partial recovery. We present here the results of a research aimed at analyzing the effects of farming typologies in respect to M. quadrifolia growth in the Po Valley area. After having transplanted M. quadrifolia swards in rice fields belonging to different farming systems, we monitored its growth and diffusion. Our results showed that M. quadrifolia has higher vegetative performance in organic farms, even though it can survive in conventional fields with reduced herbicide supply. Differences in water chemistry have limited effects on M. quadrifolia performance, because of its wide ecological amplitude. The shady conditions provided by rice canopy create micro-habitats suitable for M. quadrifolia growth. Cultivating M. quadrifolia in organic rice farms represents an important opportunity for preserving this endangered species in areas of intensive agriculture. This can, meanwhile, represent a valid opportunity to combine nature conservation and productivity offering a new possible income for farmers.

Stability studies with tigecycline in bacterial growth medium and impact of stabilizing agents - Lisa F. Amann; Emilia Ruda Vicente; Mareike Rathke; Astrid Broeker; Maria Riedner; Sebastian G. Wicha (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
Purpose This study aimed to examine the degradation of tigecycline in Mueller Hinton broth (ca-MHB), as knowledge about bacterial susceptibility is key for therapeutic decisions. Methods Antioxidative stabilizers were evaluated on tigecycline stability in a quantitative chromatography assay and tigecycline induced kill against Staphylococcus aureus (ATCC29213) was determined in time kill studies. Results Ascorbic acid caused rapid degradation of tigecycline and resulted in loss of antibacterial activity. Tigecycline was stabilized in aged broth by 2% pyruvate and bacterial growth, and tigecycline killing was similar to fresh broth without supplementation, but independent of age. Conclusion Our results underline the importance of using freshly prepared ca-MHB or the need for stabilizers for tigecycline susceptibility testing while using aged ca-MHB.

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Pharyngeal carriage rates of Neisseria meningitidis in health care professionals at a tertiary university pediatric hospital - Lisa-Maria Steurer; Mathias Hetzmannseder; Birgit Willinger; Peter Starzengruber; Claudia Mikula; Andrea Kormann-Klement; Michael Weber; Angelika Berger; Agnes Grill (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Pharyngeal carriage is the reservoir for Neisseria meningitidis in the population and the first step in disease transmission. Especially in young infants and adolescents, N. meningitidis can cause serious invasive infection with high fatality rates and high rates of long-term sequelae among survivors. The aim of this study was to determine N. meningitidis colonization rates in asymptomatic health care professionals at a tertiary university pediatric hospital and to identify risk factors for carriage. This cross-sectional meningococcal carriage survey was conducted between April and October 2018 at the Medical University of Vienna. Individuals working as nurses, pediatricians, or medical students were enrolled. Oropharyngeal swabs were directly plated onto selective agar plates and conventional culture was used for bacterial identification. Meningococcal isolates were further characterized using whole-genome sequencing. A total of 437 oropharyngeal specimens were collected. Overall, meningococcal carriage prevalence was 1.14% (5/437), with 0.7% (3/437) for capsular genotype B, and 0.5% (2/437) for capsular genotype W. Mean age of carriers was significantly lower than of non-carriers (24.2 vs. 35.8; p = 0.004). The highest carriage rate of 4.4% (4/91) was found in the age group 18–25. Carriage was negatively associated with age and timespan working in pediatrics. This is the first study evaluating the prevalence of Neisseria meningitidis carriage in health care professionals working in Pediatrics and Adolescent Medicine. Carriage was in general lower than expected for all age groups, implicating a low risk of meningococcal transmission via this population.

A novel mechanism of ACE inhibition–associated enhanced platelet reactivity: disproof of the ARB-MI paradox? - Carolin Helten; Philipp Mourikis; Lisa Dannenberg; René M’Pembele; Kajetan Trojovsky; Aysel Ayhan; Christina Kohlmorgen; Maria Grandoch; Bodo Levkau; Verena Veulemans; Tobias Petzold; Thomas Hohlfeld; et al. (European Journal of Clinical Pharmacology, 2020)

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Altered molecular signatures during kidney development after intrauterine growth restriction of different origins - Eva Nüsken; Gregor Fink; Felix Lechner; Jenny Voggel; Maria Wohlfarth; Lisa Sprenger; Nava Mehdiani; Lutz T. Weber; Max Christoph Liebau; Bent Brachvogel; Jörg Dötsch; Kai-Dietrich Nüsken (Journal of Molecular Medicine, 2020)
This study was performed to identify transcriptional alterations in male intrauterine growth restricted (IUGR) rats during and at the end of nephrogenesis in order to generate hypotheses which molecular mechanisms contribute to adverse kidney programming. IUGR was induced by low protein (LP) diet throughout pregnancy, bilateral uterine vessel ligation (LIG), or intrauterine stress (IUS) by sham operation. Offspring of unimpaired dams served as controls. Significant acute kidney damage was ruled out by negative results for proteins indicative of ER-stress, autophagy, apoptosis, or infiltration with macrophages. Renal gene expression was examined by transcriptome microarrays, demonstrating 53 (LP, n = 12; LIG, n = 32; IUS, n = 9) and 134 (LP, n = 10; LIG, n = 41; IUS, n = 83) differentially expressed transcripts on postnatal days (PND) 1 and 7, respectively. Reduced Pilra (all IUGR groups, PND 7), Nupr1 (LP and LIG, PND 7), and Kap (LIG, PND 1) as well as increased Ccl20 , S100a8/a9 (LIG, PND 1), Ifna4 , and Ltb4r2 (IUS, PND 7) indicated that inflammation-related molecular dysregulation could be a “common” feature after IUGR of different origins. Network analyses of transcripts and predicted upstream regulators hinted at proinflammatory adaptions mainly in LIG (arachidonic acid-binding, neutrophil aggregation, toll-like-receptor, NF-kappa B, and TNF signaling) and dysregulation of AMPK and PPAR signaling in LP pups. The latter may increase susceptibility towards obesity-associated kidney damage. Western blots of the most prominent predicted upstream regulators confirmed significant dysregulation of RICTOR in LP (PND 7) and LIG pups (PND 1), suggesting that mTOR-related processes could further modulate kidney programming in these groups of IUGR pups. Key messages Inflammation-related transcripts are dysregulated in neonatal IUGR rat kidneys. Upstream analyses indicate renal metabolic dysregulation after low protein diet. RICTOR is dysregulated after low protein diet and uterine vessel ligation.

Lung injury caused by exposure to the gaseous fraction of exhaust from biomass combustion (cashew nut shells): a mice model - Daniel Silveira Serra; Karla Camila Lima de Souza; Soujanya Talapala Naidu; Jéssica Rocha de Lima; Fladimir de Lima Gondim; Maria Diana Moreira Gomes; Rinaldo dos Santos Araújo; Mona Lisa Moura de Oliveira; Francisco Sales Ávila Cavalcante (Environmental Science and Pollution Research, 2020)

Pinpointing the role of Aeromonas salmonicida in the development of skin ulcerations in common dab ( Limanda limanda ) - Maaike Vercauteren; Evelien De Swaef; Annelies Maria Declercq; Johan Aerts; Bart Ampe; Snorre Gulla; Freddy Haesebrouck; Lisa Devriese; Annemie Decostere; Koen Chiers (Journal of Fish Diseases, 2020)
Aeromonas salmonicida was isolated from ulcerations in common dab ( Limanda limanda ). An experiment was performed to pinpoint its role in ulceration development, considering the importance of the skin barrier and the pigmented and non‐pigmented sides. The skin of dab was treated in three zones, one where scales and epidermis were removed, one where mucus was discarded and one non‐treated zone. Fish were tagged to allow individual identification and challenged with A. salmonicida . Mortality and severity of the developing lesions were recorded for 21 days post‐inoculation. Starting 12 days post‐inoculation, mortality occurred gradually in challenged fish; however, no direct cause could be established. Both control fish and challenged fish developed ulcerations containing A. salmonicida. S equencing of vap A gene revealed that isolates retrieved from both groups were distinct, suggesting the presence of A. salmonicida prior to the trial. Most ulcerations developed in zones where skin was removed, suggesting that abrasion might be a predisposing factor in ulceration development. Ulcerations were also observed at the insertion site of the tag, where exposed muscle tissue might have favoured the development of ulcerations . In conclusion, A. salmonicida seems to be involved in the development of skin ulcerations in dab, although the exact pathogenesis needs to be elucidated.

Virucidal effects of various agents—including protease—against koi herpesvirus and viral haemorrhagic septicaemia virus - Anette Amtmann; Ibrahim Ahmed; Petra Zahner‐Rimmel; Adam Mletzko; Lisa Katharina Jordan; Martin Oberle; Helmut Wedekind; Jürgen Christian; Sven Michael Bergmann; Anna Maria Becker (Journal of Fish Diseases, 2020)
In a search for alternative, environmentally friendly and effective disinfecting agents, a commercially available protease—Neutrase ® —was tested in this work for inactivation of koi herpesvirus (KHV) and of viral haemorrhagic septicaemia virus (VHSV). For comparison, the stability of these viral pathogens in similar configurations at various pH values and concentrations of peracetic acid or quicklime, typically used for disinfection, was tested. Therefore, virus suspensions were incubated with various concentrations of different agents for 24 hr and the titre of the remaining infectious particles was determined by virus titration. Furthermore, the treatment of both viruses, with the agents at concentrations that were previously appointed as effective, was also examined in the presence of solid material (quartz sand). All procedures investigated in this study, including the protease treatment, were able to reduce the titre of KHV and VHSV below the detection limit of the titration. Although further studies are necessary, this is the first report of the application of a protease for the inactivation of the selected fish pathogens, demonstrating the great potential of the latter for disinfection.

Corrigendum: A Response to Scientific and Societal Needs for Marine Biological Observations - Nicholas J. Bax; Patricia Miloslavich; Frank Edgar Muller-Karger; Valerie Allain; Ward Appeltans; Sonia Dawn Batten; Lisandro Benedetti-Cecchi; Pier Luigi Buttigieg; Sanae Chiba; Daniel Paul Costa; J. Emmett Duffy; Daniel C. Dunn; et al. (Frontiers in Marine Science, 2019)

Unoccupied aerial system assessment of entanglement in Northwest Atlantic gray seals ( Halichoerus grypus ) - Maria Clara Iruzun Martins; Lisa Sette; Elizabeth Josephson; Andrea Bogomolni; Kathryn Rose; Sarah M. Sharp; Misty Niemeyer; Michael Moore (Marine Mammal Science, 2019)

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies - Fabiola Ceroni; Domingo Aguilera-Garcia; Nicolas Chassaing; Dorine Arjanne Bax; Fiona Blanco-Kelly; Patricia Ramos; Maria Tarilonte; Cristina Villaverde; Luciana Rodrigues Jacy da Silva; Maria Juliana Ballesta-Martínez; Maria Jose Sanchez-Soler; Richard James Holt; et al. (Human Genetics, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

A Response to Scientific and Societal Needs for Marine Biological Observations - Nicholas J. Bax; Patricia Miloslavich; Frank Edgar Muller-Karger; Valerie Allain; Ward Appeltans; Sonia Dawn Batten; Lisandro Benedetti-Cecchi; Pier Luigi Buttigieg; Sanae Chiba; Daniel Paul Costa; J. Emmett Duffy; Daniel C. Dunn; et al. (Frontiers in Marine Science, 2019)

Management of BK-virus infection – Swedish recommendations - Tina Dalianis; Britt-Marie Eriksson; Marie Felldin; Vanda Friman; Anna-Lena Hammarin; Maria Herthelius; Per Ljungman; Johan Mölne; Lars Wennberg; Lisa Swartling (Infectious Diseases, 2019)

Successful Blue Economy Examples With an Emphasis on International Perspectives - Lu Wenhai; Caroline Cusack; Maria Baker; Wang Tao; Chen Mingbao; Kelli Paige; Zhang Xiaofan; Lisa Levin; Elva Escobar; Diva Amon; Yin Yue; Anja Reitz; et al. (Frontiers in Marine Science, 2019)

Mentoring, Training, and Scholarly Productivity Experiences of Cancer-Related Health Disparities Research Trainees: Do Outcomes Differ for Underrepresented Scientists? - Tisha M. Felder; Kathryn L. Braun; Lisa Wigfall; Maria Sevoyan; Shraddha Vyas; Samira Khan; Heather M. Brandt; Charles Rogers; Sora Tanjasiri; Cheryl A. Armstead; James R. Hébert (Journal of Cancer Education, 2019)

Methods for quantification of growth and productivity in anaerobic microbiology and biotechnology - Lisa-Maria Mauerhofer; Patricia Pappenreiter; Christian Paulik; Arne H. Seifert; Sébastien Bernacchi; Simon K.-M. R. Rittmann (Folia Microbiologica, 2019)

A response to “Personalised medicine and population health: breast and ovarian cancer” - Antonis Antoniou; Hoda Anton-Culver; Alexander Borowsky; Mireille Broeders; Jennifer Brooks; Anna Chiarelli; Jocelyne Chiquette; Jack Cuzick; Suzette Delaloge; Peter Devilee; Michael Dorval; Douglas Easton; et al. (Human Genetics, 2019)

Dose reduction, oral application, and order of intake to preserve aspirin antiplatelet effects in dipyrone co-medicated chronic artery disease patients - Lisa Dannenberg; Tobias Petzold; Alina Achilles; David Naguib; Saif Zako; Carolin Helten; René M‘Pembele; Philipp Mourikis; Yanina Podsvyadek; Maria Grandoch; Bodo Levkau; Tobias Zeus; et al. (European Journal of Clinical Pharmacology, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Advancing Marine Biological Observations and Data Requirements of the Complementary Essential Ocean Variables (EOVs) and Essential Biodiversity Variables (EBVs) Frameworks - Frank E. Muller-Karger; Patricia Miloslavich; Nicholas J. Bax; Samantha Simmons; Mark J. Costello; Isabel Sousa Pinto; Gabrielle Canonico; Woody Turner; Michael Gill; Enrique Montes; Benjamin D. Best; Jay Pearlman; et al. (Frontiers in Marine Science, 2018)

Xyris irwinii (Xyridaceae), a new cerrado species from Goiás, Brazil - Maria das Graças Lapa Wanderley; Lisa M. Campbell (Brittonia, 2018)

Scientific Considerations for the Assessment and Management of Mine Tailings Disposal in the Deep Sea - Lindsay L. Vare; Maria C. Baker; John A. Howe; Lisa A. Levin; Carlos Neira; Eva Z. Ramirez-Llodra; Amanda Reichelt-Brushett; Ashley A. Rowden; Tracy M. Shimmield; Stuart L. Simpson; Eulogio H. Soto (Frontiers in Marine Science, 2018)

Identifying Toxic Impacts of Metals Potentially Released during Deep-Sea Mining—A Synthesis of the Challenges to Quantifying Risk - Chris Hauton; Alastair Brown; Sven Thatje; Nélia C. Mestre; Maria J. Bebianno; Inês Martins; Raul Bettencourt; Miquel Canals; Anna Sanchez-Vidal; Bruce Shillito; Juliette Ravaux; Magali Zbinden; et al. (Frontiers in Marine Science, 2017)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

The marbled goby, Pomatoschistus marmoratus, as a promising species for experimental evolution studies - Lisa Locatello; Matteo Santon; Carlotta Mazzoldi; Maria B. Rasotto (Organisms Diversity & Evolution, 2017)

Females’ sampling strategy to comparatively evaluate prospective mates in the peacock blenny Salaria pavo - Lisa Locatello; Maria B. Rasotto (The Science of Nature, 2017)

Protocol for lapis lazuli provenance determination: evidence for an Afghan origin of the stones used for ancient carved artefacts kept at the Egyptian Museum of Florence (Italy) - Alessandro Lo Giudice; Debora Angelici; Alessandro Re; Gianluca Gariani; Alessandro Borghi; Silvia Calusi; Lorenzo Giuntini; Mirko Massi; Lisa Castelli; Francesco Taccetti; Thomas Calligaro; Claire Pacheco; et al. (Archaeological and Anthropological Sciences, 2017)

A model of signal processing at the isolated hair cell of the frog semicircular canal - Rita Canella; Marta Martini; Maria Lisa Rossi (Journal of Computational Neuroscience, 2017)

Fornix deep brain stimulation induced long-term spatial memory independent of hippocampal neurogenesis - Sarah Hescham; Yasin Temel; Sandra Schipper; Mélanie Lagiere; Lisa-Maria Schönfeld; Arjan Blokland; Ali Jahanshahi (Brain Structure and Function, 2017)

The key role played by charge in the interaction of cytochrome c with cardiolipin - Federica Sinibaldi; Lisa Milazzo; Barry D. Howes; Maria Cristina Piro; Laura Fiorucci; Fabio Polticelli; Paolo Ascenzi; Massimo Coletta; Giulietta Smulevich; Roberto Santucci (JBIC Journal of Biological Inorganic Chemistry, 2017)

Participation of low-income women in genetic cancer risk assessment and BRCA 1/2 testing: the experience of a safety-net institution - Ian K. Komenaka; Jesse N. Nodora; Lisa Madlensky; Lisa M. Winton; Meredith A. Heberer; Richard B. Schwab; Jeffrey N. Weitzel; Maria Elena Martinez (Journal of Community Genetics, 2016)

Back Analysis of the 2014 San Leo Landslide Using Combined Terrestrial Laser Scanning and 3D Distinct Element Modelling - Margherita Cecilia Spreafico; Mirko Francioni; Federico Cervi; Doug Stead; Gabriele Bitelli; Monica Ghirotti; Valentina Alena Girelli; Claudio Corrado Lucente; Maria Alessandra Tini; Lisa Borgatti (Rock Mechanics and Rock Engineering, 2016)

Interactions between the endocannabinoid and nicotinic cholinergic systems: preclinical evidence and therapeutic perspectives - Maria Scherma; Anna Lisa Muntoni; Miriam Melis; Liana Fattore; Paola Fadda; Walter Fratta; Marco Pistis (Psychopharmacology, 2016)

Interdependence in rainwater management technologies: an analysis of rainwater management adoption in the Blue Nile Basin - Gebrehaweria Gebregziabher; Lisa-Maria Rebelo; Simon Langan (Environment, Development and Sustainability, 2016)

Unexpected effects of sublethal doses of insecticide on the peripheral olfactory response and sexual behavior in a pest insect - Lisa Lalouette; Marie-Anne Pottier; Marie-Anne Wycke; Constance Boitard; Françoise Bozzolan; Annick Maria; Elodie Demondion; Thomas Chertemps; Philippe Lucas; David Renault; Martine Maibeche; David Siaussat (Environmental Science and Pollution Research, 2016)

Behavioral and metabolic effects of sublethal doses of two insecticides, chlorpyrifos and methomyl, in the Egyptian cotton leafworm, Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae) - Youssef Dewer; Marie-Anne Pottier; Lisa Lalouette; Annick Maria; Matthieu Dacher; Luc P. Belzunces; Guillaume Kairo; David Renault; Martine Maibeche; David Siaussat (Environmental Science and Pollution Research, 2016)

Shift work and quality of sleep: effect of working in designed dynamic light - Hanne Irene Jensen; Jakob Markvart; René Holst; Tina Damgaard Thomsen; Jette West Larsen; Dorthe Maria Eg; Lisa Seest Nielsen (International Archives of Occupational and Environmental Health, 2016)

Occurrence and antimicrobial resistance of Salmonella strains from food of animal origin in southern Italy - Yolande T. R. Proroga; Federico Capuano; Maria Rosaria Carullo; Immacolata La Tela; Rosanna Capparelli; Lisa Barco; Vincenzo Pasquale (Folia Microbiologica, 2016)

Evidence for a causal link between adaptor protein PDZK1 downregulation and Na+/H+ exchanger NHE3 dysfunction in human and murine colitis - Sunil Yeruva; Giriprakash Chodisetti; Min Luo; Mingmin Chen; Ayhan Cinar; Lisa Ludolph; Maria Lünnemann; Julia Goldstein; Anurag Kumar Singh; Brigitte Riederer; Oliver Bachmann; Andre Bleich; et al. (Pflügers Archiv - European Journal of Physiology, 2015)

Context-dependent evaluation of prospective mates in a fish - Lisa Locatello; Federica Poli; Maria B. Rasotto (Behavioral Ecology and Sociobiology, 2015)

High glucose enhances store-operated calcium entry by upregulating ORAI/STIM via calcineurin-NFAT signalling - Nikoleta Daskoulidou; Bo Zeng; Lisa M. Berglund; Hongni Jiang; Gui-Lan Chen; Olga Kotova; Sunil Bhandari; James Ayoola; Steven Griffin; Stephen L. Atkin; Maria F. Gomez; Shang-Zhong Xu (Journal of Molecular Medicine, 2015)

The ALOS Kyoto & Carbon Initiative: enabling the mapping, monitoring and assessment of globally important wetlands - Ake Rosenqvist; Lisa-Maria Rebelo; Maycira Costa (Wetlands Ecology and Management, 2015)

Using a citizen science program to monitor coral reef biodiversity through space and time - Simone Branchini; Francesco Pensa; Patrizia Neri; Bianca Maria Tonucci; Lisa Mattielli; Anna Collavo; Maria Elena Sillingardi; Corrado Piccinetti; Francesco Zaccanti; Stefano Goffredo (Biodiversity and Conservation, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Intensive agriculture reduces soil biodiversity across Europe - Maria A. Tsiafouli; Elisa Thébault; Stefanos P. Sgardelis; Peter C. de Ruiter; Wim H. van der Putten; Klaus Birkhofer; Lia Hemerik; Franciska T. de Vries; Richard D. Bardgett; Mark Vincent Brady; Lisa Bjornlund; Helene Bracht Jørgensen; et al. (Global Change Biology, 2015)
Soil biodiversity plays a key role in regulating the processes that underpin the delivery of ecosystem goods and services in terrestrial ecosystems. Agricultural intensification is known to change the diversity of individual groups of soil biota, but less is known about how intensification affects biodiversity of the soil food web as a whole, and whether or not these effects may be generalized across regions. We examined biodiversity in soil food webs from grasslands, extensive, and intensive rotations in four agricultural regions across Europe: in Sweden, the UK , the Czech Republic and Greece. Effects of land‐use intensity were quantified based on structure and diversity among functional groups in the soil food web, as well as on community‐weighted mean body mass of soil fauna. We also elucidate land‐use intensity effects on diversity of taxonomic units within taxonomic groups of soil fauna. We found that between regions soil food web diversity measures were variable, but that increasing land‐use intensity caused highly consistent responses. In particular, land‐use intensification reduced the complexity in the soil food webs, as well as the community‐weighted mean body mass of soil fauna. In all regions across Europe, species richness of earthworms, Collembolans, and oribatid mites was negatively affected by increased land‐use intensity. The taxonomic distinctness, which is a measure of taxonomic relatedness of species in a community that is independent of species richness, was also reduced by land‐use intensification. We conclude that intensive agriculture reduces soil biodiversity, making soil food webs less diverse and composed of smaller bodied organisms. Land‐use intensification results in fewer functional groups of soil biota with fewer and taxonomically more closely related species. We discuss how these changes in soil biodiversity due to land‐use intensification may threaten the functioning of soil in agricultural production systems.

Preliminary differences in peripheral immune markers and brain metabolites between fatigued and non-fatigued breast cancer survivors: a pilot study - Suzanna Maria Zick; Heather Zwickey; Lisa Wood; Bradley Foerster; Tohfa Khabir; Benjamin Wright; Eric Ichesco; Ananda Sen; Richard Edmund Harris (Brain Imaging and Behavior, 2014)

Poor vigilance affects attentional orienting triggered by central uninformative gaze and arrow cues - Andrea Marotta; Diana Martella; Lisa Maccari; Mara Sebastiani; Maria Casagrande (Cognitive Processing, 2014)

Laurdan Monitors Different Lipids Content in Eukaryotic Membrane During Embryonic Neural Development - Gabriele Bonaventura; Maria Luisa Barcellona; Ottavia Golfetto; Jamison L. Nourse; Lisa A. Flanagan; Enrico Gratton (Cell Biochemistry and Biophysics, 2014)

Effects of sleep loss on emotion recognition: a dissociation between face and word stimuli - Lisa Maccari; Diana Martella; Andrea Marotta; Mara Sebastiani; Nerisa Banaj; Luis J. Fuentes; Maria Casagrande (Experimental Brain Research, 2014)

Genetic differentiation over a short water barrier in the Brazilian tanager, Ramphocelus bresilius (Passeriformes: Thraupidae) an endemic species of the Atlantic forest, Brazil - Denise M. Nogueira; Lisa C. Pope; Terry Burke; Maria Alice S. Alves (Conservation Genetics, 2014)

Risk-sensitive resource defense in a territorial reef fish - Carley R. Schacter; Lindsey B. Albright; Elizabeth A. Dubofsky; Jessica N. Fitzsimmons; Rebecca Focht; Lauren E. Nadler; Maria Sandercock; Lauren Taylor; David Walfoort; Torrey Whitten; Lisa J. Williams; Gil G. Rosenthal (Environmental Biology of Fishes, 2014)

In Vitro and In Vivo Neuronal Electrotaxis: A Potential Mechanism for Restoration? - Ali Jahanshahi; Lisa-Maria Schönfeld; Evi Lemmens; Sven Hendrix; Yasin Temel (Molecular Neurobiology, 2014)

Genotypic and phenotypic diversity of Pediococcus pentosaceus strains isolated from food matrices and characterisation of the penocin operon - Maria Elena Martino; Michela Maifreni; Marilena Marino; Ingrid Bartolomeoli; Lisa Carraro; Luca Fasolato; Barbara Cardazzo (Antonie van Leeuwenhoek, 2013)

Novel, panzootic and hybrid genotypes of amphibian chytridiomycosis associated with the bullfrog trade - LISA M. SCHLOEGEL; LUÍS FELIPE TOLEDO; JOYCE E. LONGCORE; SASHA E. GREENSPAN; CONRADO AUGUSTO VIEIRA; MARIA LEE; SERENA ZHAO; CATHERINE WANGEN; CLAUDIA MARIS FERREIRA; MÁRCIO HIPOLITO; ANGELA J. DAVIES; CHRISTINA A. CUOMO; et al. (Molecular Ecology, 2012)
Global amphibian declines are linked with the presence of specific, highly virulent genotypes of the emerging fungal disease chytridiomycosis caused by Batrachochytrium dendrobatidis ( Bd ) known as the global panzootic lineage ( Bd ‐GPL). The global trade in amphibians for human consumption is suspected to have facilitated emergence of the disease, but evidence to support this is largely lacking. Here, we investigated the role the Lithobates catesbeianus (North American bullfrog) trade in spreading Bd genotypes by comparing strains associated with L. catesbeianus to a global panel using 36 sequenced loci from multiple chromosomal regions. Most bullfrogs were infected with Bd ‐GPL genotypes, but we also detected novel, highly divergent Bd genotypes ( Bd ‐Brazil) from a live bullfrog in a US market and from native Brazilian anurans in the Atlantic Forest where bullfrogs are widely farmed. Sexual reproduction was also detected for the first time in Bd in the form of a hybrid genotype between the Bd‐ GPL and Bd ‐Brazil lineages in the Atlantic Forest. Despite the demonstration that ribosomal RNA types in Bd fail to undergo concerted evolution (over 20 sequence types may be found in a single strain), the Bd‐ GPL and Bd ‐Brazil lineages form largely separate clusters of related internal transcribed spacer (ITS) RNA sequences. Using ITS sequences, we then demonstrate the presence of Bd ‐Brazil in Japan, primarily on invasive L. catesbeianus . The finding that Bd is capable of sexual reproduction between panzootic and endemic genotypes emphasizes the risk of international wildlife trade as a source of additional Bd epizootics owing to hybridization.

One trait, many signals: different information on male quality is enclosed within the same trait in a blenny fish - Lisa Locatello; Matteo Pizzolon; Maria Berica Rasotto (The Science of Nature, 2012)

Linking male qualities to multiple display traits: an example in a fish with exclusive male care - Matteo Pizzolon; Lisa Locatello; Robert R. Warner; Nicole Chimento; Livio Finos; Maria B. Rasotto (Behavioral Ecology and Sociobiology, 2012)

A study of wetland hydrology and ecosystem service provision: GaMampa wetland, South Africa - Matthew McCartney; Sylvie Morardet; Lisa-Maria Rebelo; C. Max Finlayson; Mutsa Masiyandima (Hydrological Sciences Journal, 2011)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

A survey of environmental pollutants and cellular-stress markers of Porites astreoides at six sites in St. John, U.S. Virgin Islands - Craig A. Downs; Cheryl M. Woodley; John E. Fauth; Sean Knutson; Martina Maria Burtscher; Lisa A. May; Athena R. Avadanei; Julie L. Higgins; Gary K. Ostrander (Ecotoxicology, 2011)

Epidemiological and clinical characteristics of pediatric gastroenteritis associated with new viral agents - Sara Giordana Rimoldi; Fabrizio Stefani; Cristina Pagani; Lisa Lucia Chenal; Nadia Zanchetta; Ilaria Di Bartolo; Alessandra Lombardi; Franco Maria Ruggeri; Dario Di lillo; Gian Vincenzo Zuccotti; Maria Rita Gismondo (Archives of Virology, 2011)

The Dayton legacy: baselines, benchmarks, climate, disturbance and proof - Lisa A. Levin; Maria Cristina Gambi; James P. Barry; Amatzia Genin; Simon Thrush (Marine Ecology, 2011)

Platinum(II) chloride indenyl complexes: electrochemical and biological evaluation - Lisa Dalla Via; Saverio Santi; Vito Di Noto; Alfonso Venzo; Enzo Agostinelli; Annarica Calcabrini; Maria Condello; Antonio Toninello (JBIC Journal of Biological Inorganic Chemistry, 2011)

Heavy Metal (Hg, Cr, Cd, and Pb) Contamination in Urban Areas and Wildlife Reserves: Honeybees as Bioindicators - Monia Perugini; Maurizio Manera; Lisa Grotta; Maria Cesarina Abete; Renata Tarasco; Michele Amorena (Biological Trace Element Research, 2011)

Diversity of the arctic deep-sea benthos - Bluhm A. Bodil; William G. Ambrose; Melanie Bergmann; Lisa M. Clough; Andrey V. Gebruk; Christiane Hasemann; Katrin Iken; Michael Klages; Ian R. MacDonald; Paul E. Renaud; Ingo Schewe; Thomas Soltwedel; et al. (Marine Biodiversity, 2011)

Maternal consumption of coffee and tea during pregnancy and risk of childhood ALL: results from an Australian case–control study - Elizabeth Milne; Jill A. Royle; Lisa C. Bennett; Nicholas H. de Klerk; Helen D. Bailey; Carol Bower; Margaret Miller; John Attia; Rodney J. Scott; Maria Kirby; Bruce K. Armstrong (Cancer Causes & Control, 2011)

An Rhs-like genetic element is involved in bacteriocin production by Pseudomonas savastanoi pv. savastanoi - Angelo Sisto; Maria Grazia Cipriani; Maria Morea; Stella Lisa Lonigro; Francesca Valerio; Paola Lavermicocca (Antonie van Leeuwenhoek, 2010)

Derivation of Man-1 and Man-2 research grade human embryonic stem cell lines - Maria V. Camarasa; Robbie W. Kerr; Sharon F. Sneddon; Nicola Bates; Lisa Shaw; Rachel A. Oldershaw; Fiona Small; Melissa A. Baxter; Tristan R. Mckay; Daniel R. Brison; Susan J. Kimber (In Vitro Cellular & Developmental Biology - Animal, 2010)

Biomarker responses in the crab Carcinus aestuarii to assess environmental pollution in the Lagoon of Venice (Italy) - Lisa Locatello; Valerio Matozzo; Maria Gabriella Marin (Ecotoxicology, 2009)

The Zea mays b-32 ribosome-inactivating protein efficiently inhibits growth of Fusarium verticillioides on leaf pieces in vitro - Chiara Lanzanova; Maria Gabriella Giuffrida; Mario Motto; Cristina Baro; Guenter Donn; Hans Hartings; Elisabetta Lupotto; Maria Careri; Lisa Elviri; Carlotta Balconi (European Journal of Plant Pathology, 2009)

Isolation and possible role of fast and slow potassium current components in hair cells dissociated from frog crista ampullaris - Marta Martini; Rita Canella; Riccardo Fesce; Maria Lisa Rossi (Pflügers Archiv - European Journal of Physiology, 2009)

Conservation value of an exotic species: the case of coconuts on the Kayapo indigenous lands, south-eastern Amazonia - Rodolfo Salm; Lisa Feder; Mario Augusto Gonçalves Jardim; Nefertiti Hass; Euphly Jalles-Filho; Ana Maria Costa (Environment, Development and Sustainability, 2009)

Cerebellum and Detection of Sequences, from Perception to Cognition - Marco Molinari; Francesca R. Chiricozzi; Silvia Clausi; Anna Maria Tedesco; Mariagrazia De Lisa; Maria G. Leggio (The Cerebellum, 2008)

Turner syndrome mosaicism: an unusual case with a de novo large dicentric marker chromosome: mos 45,X/46,X, ter rea(X;X)(p22.3;p22.3) - Anna Lisa Nucaro; Paola Melis; Maria Rosaria Casini; Rossano Rossino; Milena Cau; Maria Antonietta Melis; Sandro Loche (Journal of Applied Genetics, 2008)

Whole‐genome analysis of the ammonia‐oxidizing bacterium, Nitrosomonas eutropha C91: implications for niche adaptation - Lisa Y. Stein; Daniel J. Arp; Paul M. Berube; Patrick S. G. Chain; Loren Hauser; Mike S. M. Jetten; Martin G. Klotz; Frank W. Larimer; Jeanette M. Norton; Huub J. M. Op den Camp; Maria Shin; Xueming Wei (Environmental Microbiology, 2007)
Summary Analysis of the structure and inventory of the genome of Nitrosomonas eutropha C91 revealed distinctive features that may explain the adaptation of N. eutropha ‐like bacteria to N‐saturated ecosystems. Multiple gene‐shuffling events are apparent, including mobilized and replicated transposition, as well as plasmid or phage integration events into the 2.66 Mbp chromosome and two plasmids (65 and 56 kbp) of N. eutropha C91. A 117 kbp genomic island encodes multiple genes for heavy metal resistance, including clusters for copper and mercury transport, which are absent from the genomes of other ammonia‐oxidizing bacteria (AOB). Whereas the sequences of the two ammonia monooxygenase and three hydroxylamine oxidoreductase gene clusters in N. eutropha C91 are highly similar to those of Nitrosomonas europaea ATCC 19718, a break of synteny in the regions flanking these clusters in each genome is evident. Nitrosomonas eutropha C91 encodes four gene clusters for distinct classes of haem‐copper oxidases, two of which are not found in other aerobic AOB. This diversity of terminal oxidases may explain the adaptation of N. eutropha to environments with variable O 2 concentrations and/or high concentrations of nitrogen oxides. As with N. europaea , the N. eutropha genome lacks genes for urease metabolism, likely disadvantaging nitrosomonads in low‐nitrogen or acidic ecosystems. Taken together, this analysis revealed significant genomic variation between N. eutropha C91 and other AOB, even the closely related N. europaea , and several distinctive properties of the N. eutropha genome that are supportive of niche specialization.

Ca2+ current of frog vestibular hair cells is modulated by intracellular ATP but not by long-lasting depolarisation - Marta Martini; Federica Farinelli; Maria Lisa Rossi; Giorgio Rispoli (European Biophysics Journal, 2007)

Heme oxygenase 1 expression in rat liver during ageing and ethanol intoxication - Stefania Patriarca; Anna Lisa Furfaro; Luana Cosso; Elena Pesce Maineri; Emanuela Balbis; Cinzia Domenicotti; Mariapaola Nitti; Damiano Cottalasso; Umberto Maria Marinari; Maria Adelaide Pronzato; Nicola Traverso (Biogerontology, 2007)

Critical Active-Site Residues Identified by Site-Directed Mutagenesis in Pseudomonas aeruginosa Phosphorylcholine Phosphatase, A New Member of the Haloacid Dehalogenases Hydrolase Superfamily - Paola R. Beassoni; Lisandro H. Otero; Maria J. Massimelli; Angela T. Lisa; Carlos E. Domenech (Current Microbiology, 2006)

Alcohol Dehydrogenase 3, Glutathione S-transferase M1 and T1 Polymorphisms, Alcohol Consumption and Hepatocellular Carcinoma (Italy) - Loredana Covolo; Umberto Gelatti; Renato Talamini; Seymour Garte; Paola Trevisi; Silvia Franceschi; Michela Franceschini; Fabio Barbone; Alessandro Tagger; Maria Lisa Ribero; Giovanni Parrinello; Valter Donadon; et al. (Cancer Causes & Control, 2005)

Kristian Fauchald: A Tribute - Greg W. Rouse; Maria Cristina Gambi; Lisa A. Levin (Marine Ecology, 2005)

Occupational class, occupational mobility and cancer incidence among middle-aged men and women: a prospective study of the French GAZEL cohort* - Maria Melchior; Marcel Goldberg; Nancy Krieger; Ichiro Kawachi; Gwenn Menvielle; Marie Zins; Lisa F. Berkman (Cancer Causes & Control, 2005)

‘Back to the future’ - Maria Cristina Gambi; Lisa Ann Levin (Marine Ecology, 2005)

Intrahepatic cholangiocarcinoma and hepatitis C and B virus infection, alcohol intake, and hepatolithiasis: a case–control study in Italy - Francesco Donato; Umberto Gelatti; Alessandro Tagger; Maurizio Favret; Maria Lisa Ribero; Francesco Callea; Claudia Martelli; Antonella Savio; Paola Trevisi; Giuseppe Nardi (Cancer Causes & Control, 2001)

Probiotics: from myth to reality. Demonstration of functionality in animal models of disease and in human clinical trials - Colum Dunne; Lisa Murphy; Sarah Flynn; Liam O'Mahony; Sile O'Halloran; Maria Feeney; Darrin Morrissey; Gerardine Thornton; Gerald Fitzgerald; Charles Daly; Barry Kiely; Eamonn M. M. Quigley; et al. (Antonie van Leeuwenhoek, 1999)

A case–control study on family history of liver cancer as a risk factor for hepatocellular carcinoma in North Italy - Francesco Donato; Umberto Gelatti; Roberta Chiesa; Alberto Albertini; Elena Bucella; Paolo Boffetta; Alessandro Tagger; Maria Lisa Ribero; Giuseppe Portera; Michele Fasola; Giuseppe Nardi (Cancer Causes & Control, 1999)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)